Resin composition
By adding the acid salt of the amine compound represented by formula (I) to the maleimide resin composition, the problems of lowering adhesion strength and lowering of glass transition temperature after accelerated environmental tests are solved, and efficient adhesion is achieved Strength maintenance and high glass transition temperature.
Patent Information
- Application Number
- CN202411008485.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-28
- Filing Date
- 2024-07-25
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to maintain the copper foil bond strength and maintain a high glass transition temperature after accelerating environmental test (HAST).
The maleimide resin composition is added to the acid salt of the amine compound represented by formula (I) to inhibit the diffusion of moisture and prevent the oxidation reaction.
It is achieved that the copper foil bonding strength remains maintained after accelerating environmental test (HAST) and a high glass transition temperature is maintained.
Smart Images

Figure CN119432073A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition containing a maleimide resin and also to a resin sheet, a printed wiring board and a semiconductor device obtained by using the resin composition. Background Art
[0002] As a manufacturing technology for printed wiring boards, a manufacturing method using a buildup method in which insulating layers and conductive layers are alternately stacked is known. In the manufacturing method using the buildup method, the insulating layer is formed by curing a resin composition containing a maleimide resin, for example.
[0003] Generally speaking, maleimide resin has low dielectric properties, but there is a problem that the adhesion strength after accelerated environmental test (HAST) is reduced if a pyridine-based curing accelerator is used. On the other hand, if an imidazole-based curing accelerator is used, the above-mentioned problem can be avoided, but due to low catalytic ability, there is a problem of lowering the glass transition temperature (Tg).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 7197067 Summary of the invention
[0007] Problems to be solved by the invention
[0008] An object of the present invention is to provide a resin composition that can provide a cured product that maintains excellent copper foil adhesion strength even after a HAST test and has a high glass transition temperature.
[0009] Technical solutions to solve problems
[0010] In order to solve the problem of the present invention, the present inventors conducted intensive studies and found that by including an acid salt of an amine compound represented by formula (I) described below in a maleimide resin composition, it is unexpectedly possible to inhibit the diffusion of moisture into the resin, prevent oxidation caused by heat and moisture in an accelerated environmental test (HAST), and obtain a cured product having an excellent copper foil adhesion strength and a high glass transition temperature even after an accelerated environmental test (HAST), thereby completing the present invention.
[0011] That is, the present invention includes the following contents.
[0012] [1] A resin composition comprising (A) a maleimide resin and (B) an acid salt of an amine compound represented by formula (I),
[0013]
[0014] In the formula, R 1 , R 2 , R 3 , R 4 and R 5 Each independently represents a hydrogen atom or a substituent.
[0015] [2] The resin composition according to [1] above, wherein the amine compound represented by formula (I) is 4-dimethylaminopyridine.
[0016] [3] The resin composition according to [1] or [2] above, wherein the component (B) comprises a salt of an amine compound represented by formula (I) and an organic acid selected from carboxylic acids and sulfonic acids.
[0017] [4] The resin composition according to any one of [1] to [3] above, wherein the component (B) comprises a salt of an amine compound represented by formula (I) and an organic acid represented by any one of formulas (IIa) to (IIc),
[0018] [Chemistry 2]
[0019]
[0020] In the formula,
[0021] X represents -CO- or -SO2-,
[0022] R a , R b , R c , R d , R e , R f and R g Each independently represents a hydrogen atom or a substituent.
[0023] [5] The resin composition according to any one of [1] to [4] above, wherein the component (B) comprises an amine compound represented by the formula (I) having an acid dissociation constant (pK a ) is 3.0 or less, and in the case of a polybasic organic acid, the acid dissociation constant (pK a ) is the lowest acid dissociation constant (pK) in the first stage a1 ).
[0024] [6] The resin composition according to any one of [1] to [5] above, wherein the component (B) comprises a salt of an amine compound represented by formula (I) and an organic acid selected from phthalic acid, trimellitic acid and p-toluenesulfonic acid.
[0025] [7] The resin composition according to any one of [1] to [6] above, wherein the mass ratio of the component (B) to the component (A), i.e., the content of the component (B) / the content of the component (A), is 0.001 to 0.1.
[0026] [8] The resin composition according to any one of [1] to [7] above, further comprising (C) an inorganic filler.
[0027] [9] The resin composition according to [8] above, wherein the component (C) contains silica.
[0028]
[10] The resin composition according to [8] or [9] above, wherein the content of the component (C) is 40% by mass or more when the nonvolatile component in the resin composition is 100% by mass.
[0029]
[11] The resin composition according to any one of [1] to
[10] above, wherein the content of the anionic polymerizable curing agent (D) is 0% by mass to 20% by mass when the nonvolatile component in the resin composition is 100% by mass.
[0030]
[12] The resin composition according to any one of [1] to
[11] above, wherein the content of the epoxy resin (E) is 0% by mass to 20% by mass when the non-volatile component in the resin composition is 100% by mass.
[0031]
[13] The resin composition according to any one of [1] to
[12] above, wherein the content of the (F) thermoplastic resin is 0% to 30% by mass when the non-volatile component in the resin composition is 100% by mass.
[0032]
[14] The resin composition according to any one of [1] to
[13] above, wherein a cured product of the resin composition has a glass transition temperature (Tg) of 140° C. or higher.
[0033]
[15] The resin composition according to any one of [1] to
[14] above, which is used for forming an insulating layer of a printed wiring board.
[0034]
[16] A cured product of the resin composition layer according to any one of [1] to
[15] above.
[0035]
[17] A resin sheet comprising a support and a resin composition layer formed from the resin composition according to any one of [1] to
[15] above and provided on the support.
[0036]
[18] A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to any one of [1] to
[15] above.
[0037]
[19] A semiconductor device comprising the printed wiring board described in
[18] above.
[0038]
[20] A maleimide resin curing accelerator, comprising an acid salt of an amine compound represented by formula (I),
[0039]
[0040] In the formula, R 1 , R 2 , R 3 , R 4 and Rw each independently represent a hydrogen atom or a substituent.
[0041] Effects of the Invention
[0042] According to the resin composition of the present invention, a cured product can be obtained which can maintain excellent copper foil adhesion strength even after a HAST test and has a high glass transition temperature. DETAILED DESCRIPTION
[0043] Hereinafter, the present invention will be described in detail with reference to its preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and any changes can be made within the scope of the claims of the present invention and their equivalents.
[0044] <Resin composition>
[0045] The resin composition of the present invention comprises (A) a maleimide resin and (B) an acid salt of an amine compound represented by formula (I). According to such a resin composition, a cured product having a high glass transition temperature and maintaining excellent copper foil adhesion strength even after a HAST test can be obtained.
[0046] The resin composition of the present invention may further contain any component in addition to (A) maleimide resin and (B) acid salt of an amine compound represented by formula (I). Examples of the optional component include (C) inorganic filler, (D) anionic polymerizable curing agent, (E) epoxy resin, (F) thermoplastic resin, and (G) free radical polymerization initiator.
[0047] Hereinafter, each component contained in the resin composition will be described in detail.
[0048] <(A) Maleimide resin>
[0049] The resin composition of the present invention contains (A) a maleimide resin. The maleimide resin (A) may be used alone or in combination of two or more. The maleimide resin (A) has one or more maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl) in one molecule.
[0050] (A) The maleimide resin may be an aromatic maleimide resin having a maleimide group directly bonded to an aromatic ring, or an aliphatic maleimide resin having no maleimide group directly bonded to an aromatic ring, but preferably includes an aromatic maleimide resin.
[0051] The (A) maleimide resin is not particularly limited, and examples thereof include maleimide resins having a biphenyl skeleton, maleimide resins having an indane skeleton, maleimide resins having a bismaleimide diphenylmethane skeleton, maleimide resins having a carbon skeleton derived from a dimer acid, and maleimide resins having an aromatic polyether ketone skeleton.
[0052] The carbon skeleton derived from dimer acid refers to a carbon skeleton formed by removing the two terminal carboxyl groups (-COOH) of dimer acid, or a carbon skeleton formed by replacing the two terminal carboxyl groups (-COOH) with methylene groups (-CH2-). Dimer acid is a known compound obtained by dimerizing unsaturated fatty acids (preferably unsaturated fatty acids with 11 to 22 carbon atoms, more preferably unsaturated fatty acids with 14 to 20 carbon atoms, and particularly preferably unsaturated fatty acids with 18 carbon atoms), and its industrial manufacturing process is basically standardized in the industry. For dimer acid, a substance with a carbon number of 36 dimer acid obtained by dimerizing unsaturated fatty acids with 18 carbon atoms such as oleic acid and linoleic acid, which are particularly low-cost and easily available, as the main component can be easily obtained. In addition, dimer acid sometimes contains any amount of monomeric acid, trimer acid, other polymerized fatty acids, etc., depending on the manufacturing method, the degree of purification, etc. In addition, although double bonds remain after the polymerization reaction of unsaturated fatty acids, in the present specification, hydrogenated products in which the degree of unsaturation is reduced by further hydrogenation reaction are also considered to be included in dimer acids.
[0053] The maleimide resin having a carbon skeleton derived from a dimer acid preferably comprises a maleimide resin represented by formula (1),
[0054] [Chemistry 4]
[0055]
[0056] [Wherein,
[0057] n+1 Xs each independently represent a divalent organic group formed by 5 or more backbone atoms selected from carbon atoms, nitrogen atoms (nitrogen atoms that do not form imide), oxygen atoms and sulfur atoms, and non-backbone atoms selected from hydrogen atoms and halogen atoms, and at least one of the n+1 Xs represents a divalent hydrocarbon group derived from a dimer acid;
[0058] n Ys each independently represent a tetravalent organic group consisting of five or more backbone atoms selected from carbon atoms, nitrogen atoms (nitrogen atoms that do not form imide), oxygen atoms and sulfur atoms, and non-backbone atoms selected from hydrogen atoms and halogen atoms;
[0059] n represents an integer of 0 or 1 or more].
[0060] The n+1 Xs independently represent a divalent organic group formed by 5 or more (preferably 5 to 200, more preferably 5 to 100, and further preferably 5 to 50) backbone atoms selected from carbon atoms, nitrogen atoms (nitrogen atoms that do not form imide), oxygen atoms and sulfur atoms, and non-backbone atoms selected from hydrogen atoms and halogen atoms, and at least one of the n+1 Xs represents a divalent hydrocarbon group derived from a dimer acid.
[0061] The halogen atom refers to a fluorine atom, a chlorine atom, a bromine atom or an iodine atom.
[0062] The divalent hydrocarbon group derived from a dimer acid refers to a divalent hydrocarbon group obtained by removing two terminal carboxyl groups (—COOH) of a dimer acid or replacing two terminal carboxyl groups (—COOH) with methylene groups (—CH 2 —).
[0063] The n+1 Xs may have a divalent organic group other than a divalent hydrocarbon group derived from a dimer acid. When the n+1 Xs are set to 100 mol %, it is preferred that 30 mol % or more of them are divalent hydrocarbon groups derived from a dimer acid, more preferably 60 mol % or more are divalent hydrocarbon groups derived from a dimer acid, further preferably 90 mol % or more are divalent hydrocarbon groups derived from a dimer acid, and it is particularly preferred that (all) the n+1 Xs are divalent hydrocarbon groups derived from a dimer acid.
[0064] The divalent organic group other than the divalent hydrocarbon group derived from the dimer acid among the n+1 Xs may be a divalent organic group not having an aromatic ring or a divalent organic group having an aromatic ring.
[0065] The n Ys independently represent a tetravalent organic group formed by 5 or more (preferably 5 to 200, more preferably 5 to 100, and further preferably 5 to 50) backbone atoms selected from carbon atoms, nitrogen atoms (nitrogen atoms that do not form imide), oxygen atoms, and sulfur atoms, and non-backbone atoms selected from hydrogen atoms and halogen atoms. The tetravalent organic group represented by Y may be a tetravalent organic group without an aromatic ring or a tetravalent organic group with an aromatic ring.
[0066] In one embodiment, the tetravalent organic group represented by Y is preferably a group selected from the group consisting of formulae (Y1) to (Y5),
[0067] [Chemistry 5]
[0068]
[0069] [Wherein,
[0070] Ring Y 11 , Ring Y 21 , Ring Y 22 , Ring Y 31 , Ring Y 32 , Ring Y 33 , Ring Y 41 , Ring Y 42 , Ring Y 43 , Ring Y 44 , Ring Y 51 , Ring Y 52 , Ring Y 53 , Ring Y 54 and Ring Y 55 Each independently represents an aromatic ring which may have a substituent, or a non-aromatic ring which may have a substituent;
[0071] Y 2a , Y 3a , Y 3b , Y 4a , Y 4b , Y 4c , Y 5a , Y 5b , Y 5c and Y 5d Each independently represents a single bond, -C(Ry)2-, -O-, -CO-, -S-, -SO-, -SO2-, -CONH-, or -NHCO-;
[0072] Ry each independently represents a hydrogen atom, or an alkyl group which may be substituted with a halogen atom, or two Ry groups bonded to the same carbon atom are bonded together to form a non-aromatic ring which may have a substituent;
[0073] * indicates a bonding site]. It should be noted that the two bonding sites on the same ring indicated by * are bonding sites to two adjacent carbon atoms on the ring, respectively.
[0074] Ring Y 11 , Ring Y 21 , Ring Y 22 , Ring Y 31 , Ring Y 32 , Ring Y 33 , Ring Y 41 , Ring Y 42 , Ring Y 43 , Ring Y 44 , Ring Y 51 , Ring Y 52 , Ring Y 33 , Ring Y 54 and Ring Y 55 Each independently represents an aromatic ring which may have a substituent, or a non-aromatic ring which may have a substituent; in one embodiment, the aromatic ring which may have a substituent is preferred, the benzene ring which may have a substituent is more preferred, and the benzene ring which may be substituted with an alkyl group is further preferred.
[0075] An aromatic ring refers to a ring that follows Huckel's rule in which the number of electrons contained in the π electron system on the ring is 4p+2 (p is a natural number). The aromatic ring may be an aromatic carbocyclic ring having only carbon atoms as ring atoms, or an aromatic heterocyclic ring having heteroatoms such as oxygen atoms, nitrogen atoms, and sulfur atoms in addition to carbon atoms as ring atoms. In one embodiment, the aromatic ring is preferably an aromatic carbocyclic ring. In one embodiment, the aromatic ring is preferably an aromatic ring of 5 to 14 members, more preferably an aromatic ring of 6 to 14 members, and further preferably an aromatic ring of 6 to 10 members. Preferred specific examples of aromatic rings (aromatic carbocyclic rings) include benzene rings, naphthalene rings, anthracene rings, phenanthrene rings, etc., preferably benzene rings or naphthalene rings, and particularly preferably benzene rings.
[0076] The non-aromatic ring refers to a ring other than an aromatic ring having aromaticity as a whole. The non-aromatic ring may be a non-aromatic carbocyclic ring having only carbon atoms as ring atoms, or a non-aromatic heterocyclic ring having heteroatoms such as oxygen atoms, nitrogen atoms, and sulfur atoms as ring atoms in addition to carbon atoms. In one embodiment, the non-aromatic ring is preferably a non-aromatic carbocyclic ring. The non-aromatic ring may be a saturated ring or an unsaturated ring. The non-aromatic ring is preferably a 3-21-membered non-aromatic ring, more preferably a 4-17-membered non-aromatic ring, and further preferably a 5-14-membered non-aromatic ring. Preferred specific examples of the non-aromatic ring (non-aromatic carbocyclic ring) include non-aromatic saturated carbocyclic rings of monocyclic systems such as cyclobutane ring, cyclopentane ring, cyclohexane ring, cycloheptane ring, and cyclooctane ring; non-aromatic unsaturated carbocyclic rings of monocyclic systems such as cyclobutene ring, cyclopentene ring, cyclohexene ring, cycloheptene ring, cyclooctene ring, cyclopentadiene ring, and cyclohexadiene ring; bicyclo[2.2.1]heptane ring (norbornane ring), bicyclo[4.4.0]decane ring (decalin ring), bicyclo[5.3.0]decane ring, bicyclo[4.3.0]nonane ring (hexahydroindan ring), bicyclo[3.2.1]octane ring, bicyclo[5.4.0]undecane ring, bicyclo[3.3.0]octane ring, bicyclo[3.3.1]nonane ring, tricyclo[5.2.1.0 2,6 ] decane ring (tetrahydrodicyclopentadiene ring), tricyclo[3.3.1.1 3,7 ] decane ring (adamantane ring), tricyclic [6.2.1.0 2,7 The non-aromatic ring may be a non-aromatic ring partially fused with an aromatic ring. Examples of the non-aromatic ring partially fused with an aromatic ring include an indane ring, an indene ring, a tetralin ring, a 1,2-dihydronaphthalene ring, a 1,4-dihydronaphthalene ring, a fluorene ring, a 9,10-dihydroanthracene ring, and a 9,10-dihydrophenanthrene ring.
[0077] As ring Y 11 , Ring Y 21 , Ring Y 22 , Ring Y 31 , Ring Y 32 , Ring Y 33 , Ring Y 41 , Ring Y 42 , Ring Y 43 , Ring Y 44 , Ring Y 51 , Ring Y 52 , Ring Y 53 , Ring Y 54 and Ring Y 55The "substituent" in the "aromatic ring which may have a substituent" and the "non-aromatic ring which may have a substituent" is not particularly limited, and examples thereof include halogen atoms, -NO2, -CN, -COH, -OH, -SH, -NH2, -COOH, -R, -COR, -OR, -SR, -SOR, -SO2R, -NHR, -NR2, -COOR, -OCOR, -CONH2, -CONHR, -CONR2, -NHCOR and the like monovalent substituents (wherein R each independently represents a monovalent hydrocarbon group).
[0078] A monovalent hydrocarbon group refers to a monovalent hydrocarbon group having only one or more (preferably 1 to 50, more preferably 1 to 20) carbon atoms as skeleton atoms and hydrogen atoms as non-skeleton atoms. The monovalent hydrocarbon group may be a monovalent saturated hydrocarbon group or a monovalent unsaturated hydrocarbon group. The monovalent hydrocarbon group may or may not have an aromatic structure. Examples of the monovalent hydrocarbon group include alkyl, alkenyl, aryl, aralkyl, and alkylaryl groups.
[0079] Alkyl refers to a linear, branched and / or cyclic monovalent aliphatic saturated hydrocarbon group. Unless otherwise specified, the alkyl group is preferably an alkyl group having 1 to 14 carbon atoms, more preferably an alkyl group having 1 to 10 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, and particularly preferably an alkyl group having 1 to 3 carbon atoms. Examples of the alkyl group include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, sec-pentyl, neopentyl, tert-pentyl, hexyl, isohexyl, heptyl, isoheptyl, octyl, isooctyl, tert-octyl, cyclopentyl, cyclohexyl, and cyclohexylmethyl.
[0080] Alkenyl refers to a linear, branched and / or cyclic monovalent aliphatic unsaturated hydrocarbon group having at least one non-aromatic carbon-carbon double bond. Unless otherwise specified, alkenyl is preferably an alkenyl having 2 to 14 carbon atoms, more preferably an alkenyl having 2 to 10 carbon atoms, further preferably an alkenyl having 2 to 6 carbon atoms, and particularly preferably an alkenyl having 2 or 3 carbon atoms. Examples of alkenyl include vinyl, propenyl (allyl, 1-propenyl, isopropenyl), butenyl (1-butenyl, 2-butenyl, methylallyl, isobutenyl, etc.), pentenyl (1-pentenyl, etc.), hexenyl (1-hexenyl, etc.), heptenyl (1-heptenyl, etc.), octenyl (1-octenyl, etc.), cyclopentenyl (2-cyclopentenyl, etc.), cyclohexenyl (3-cyclohexenyl), etc.
[0081] The aryl group refers to a monovalent aromatic hydrocarbon group obtained by removing one hydrogen atom from an aromatic carbon ring. Unless otherwise specified, the aryl group is preferably an aryl group having 6 to 14 carbon atoms, and more preferably an aryl group having 6 to 10 carbon atoms. Examples of the aryl group include phenyl, 1-naphthyl, and 2-naphthyl.
[0082] Aralkyl refers to an alkyl group substituted with one or more (preferably one) aryl groups. Unless otherwise specified, the aralkyl group is preferably an aralkyl group having 7 to 15 carbon atoms, and more preferably an aralkyl group having 7 to 11 carbon atoms. Examples of the aralkyl group include benzyl, phenethyl, hydrocinnamyl, α-methylbenzyl, α-cumyl, 1-naphthylmethyl, and 2-naphthylmethyl.
[0083] The alkylaryl group refers to an aryl group substituted by one or more (preferably one) alkyl groups. Unless otherwise specified, the alkylaryl group is preferably an alkylaryl group having 7 to 15 carbon atoms, and more preferably an alkylaryl group having 7 to 11 carbon atoms. Examples of the alkylaryl group include 4-methylphenyl, 3-methylphenyl, 2-methylphenyl, 4-ethylphenyl, 3-ethylphenyl, 2-ethylphenyl, 4-isopropylphenyl, 3-isopropylphenyl, and 2-isopropylphenyl.
[0084] Y 2a , Y 3a , Y 3b , Y 4a , Y 4b , Y 4c , Y 5a , Y 5b , Y 5c and Y 5d Each independently represents a single bond, -C(Ry)2-, -O-, -CO-, -S-, -SO-, -SO2-, -CONH-, or -NHCO-. In one embodiment, a single bond, -C(Ry)2-, or -O- is preferred.
[0085] Ry each independently represents a hydrogen atom, or an alkyl group which may be substituted by a halogen atom, or two Rys bonded to the same carbon atom are bonded together to form a non-aromatic ring which may have a substituent; in one embodiment, preferably a hydrogen atom, or an alkyl group which may be substituted by a halogen atom, more preferably a hydrogen atom, or a methyl group which may be substituted by a halogen atom, further preferably a hydrogen atom, a methyl group, or a trifluoromethyl group, and particularly preferably a hydrogen atom or a methyl group.
[0086] The "substituent" in the "non-aromatic ring which may have a substituent" formed by Ry is not particularly limited, and examples thereof include halogen atoms, -NO2, -CN, -COH, -OH, -SH, -NH2, -COOH, -R, -COR, -OR, -SR, -SOR, -SO2R, -NHR, -NR2, -COOR, -OCOR, -CONH2, -CONHR, -CONR2, -NHCOR and other monovalent substituents (wherein R each independently represents a monovalent hydrocarbon group).
[0087] n represents an integer of 0 or 1 or greater; in one embodiment, it is preferably 0 or an integer of 1 to 10, more preferably 0.
[0088] Examples of commercially available maleimide resins having a carbon skeleton derived from a dimer acid include "BMI-689", "BMI-1500", "BMI-1700", and "BMI-3000J" manufactured by Designer Molecules and "SLK-6895-T90" manufactured by Shin-Etsu Chemical Co., Ltd.
[0089] The maleimide resin having a bismaleimide diphenylmethane skeleton preferably comprises a maleimide compound represented by formula (2),
[0090] [Chemistry 6]
[0091]
[0092] [Wherein,
[0093] R 10 Each independently represents a hydrogen atom, or an alkyl group which may be substituted by a halogen atom;
[0094] Ring D each independently represents an aromatic carbon ring which may have a substituent;
[0095] e represents an integer greater than 1]. For the e unit, each unit may be the same or different. The maleimide resin having a bismaleimide diphenylmethane skeleton may be used alone or in combination of two or more in any ratio.
[0096] The "substituent" in ring D is not particularly limited, and examples thereof include a halogen atom, -NO2, -CN, -COH, -OH, -SH, -NH2, -COOH, -R, -COR, -OR, -SR, -SOR, -SO2R, -NHR, -NR2, -COOR, -OCOR, -CONH2, -CONHR, -CONR2, -NHCOR and the like monovalent substituents (wherein R each independently represents a monovalent hydrocarbon group).
[0097] R 10 Each independently represents a hydrogen atom or an alkyl group which may be substituted with a halogen atom, preferably a hydrogen atom or an alkyl group, more preferably a hydrogen atom or a methyl group, further preferably a hydrogen atom.
[0098] Ring D each independently represents an aromatic ring which may have a substituent, preferably a benzene ring which may have a substituent, more preferably a benzene ring which may be substituted with a group selected from an alkyl group and an aryl group, particularly preferably an (unsubstituted) benzene ring.
[0099] e represents an integer of 1 or greater, preferably an integer of 1-10.
[0100] As a commercial item of the maleimide resin which has a bismaleimidediphenylmethane skeleton, "BMI-2300" etc. are mentioned, for example, the Yamato Chemical Industry Co., Ltd.
[0101] The maleimide resin having a biphenyl skeleton preferably comprises a maleimide compound represented by formula (3),
[0102] [Chemistry 7]
[0103]
[0104] [Wherein,
[0105] R 20 Each independently represents a hydrogen atom, or an alkyl group which may be substituted by a halogen atom;
[0106] Ring E, Ring F and Ring G each independently represent an aromatic carbon ring which may have a substituent;
[0107] f represents an integer greater than 1]. For the f units, each unit may be the same or different. The maleimide resin having a biphenyl skeleton may be used alone or in combination of two or more in any ratio.
[0108] The "substituent" in Ring E, Ring F and Ring G is not particularly limited, and examples thereof include monovalent substituents such as halogen atoms, -NO2, -CN, -COH, -OH, -SH, -NH2, -COOH, -R, -COR, -OR, -SR, -SOR, -SOR, -NHR, -NR2, -COOR, -OCOR, -CONH2, -CONHR, -CONR2, and -NHCOR (wherein R each independently represents a monovalent hydrocarbon group).
[0109] R 20 Each independently represents a hydrogen atom or an alkyl group which may be substituted with a halogen atom, preferably a hydrogen atom or an alkyl group, more preferably a hydrogen atom or a methyl group, further preferably a hydrogen atom.
[0110] Ring E, ring F and ring G each independently represent an aromatic ring which may have a substituent, preferably a benzene ring which may have a substituent, more preferably a benzene ring which may be substituted by a group selected from an alkyl group and an aryl group, particularly preferably an (unsubstituted) benzene ring.
[0111] f represents an integer of 1 or greater, preferably an integer of 1-10.
[0112] Examples of commercially available products of the maleimide resin having a biphenyl skeleton include "MIR-3000-70MT" and "MIR-5000-60T" manufactured by Nippon Kayaku Co., Ltd.
[0113] The maleimide resin having an indane skeleton preferably includes a maleimide resin represented by formula (4),
[0114] [Chemistry 8]
[0115]
[0116] [Wherein,
[0117] R 30 Each independently represents an alkyl group;
[0118] Ring H and Ring I each independently represent an aromatic carbon ring which may have a substituent;
[0119] m represents an integer greater than or equal to 1]. Regarding the m units, each unit may be the same or different.
[0120] The "substituent" in Ring H and Ring I is not particularly limited, and examples thereof include halogen atoms, -NO2, -CN, -COH, -OH, -SH, -NH2, -COOH, -R, -COR, -OR, -SR, -SOR, -SO2R, -NHR, -NR2, -COOR, -OCOR, -CONH2, -CONHR, -CONR2, -NHCOR and the like monovalent substituents (wherein R each independently represents a monovalent hydrocarbon group).
[0121] R 30 Each independently represents an alkyl group, and in one embodiment, a methyl group is preferred.
[0122] Ring H each independently represents an aromatic ring which may have a substituent, and in one embodiment, is preferably a benzene ring which may have a substituent, more preferably a benzene ring which may be substituted with an alkyl group, and further preferably a benzene ring substituted with an alkyl group.
[0123] Ring I each independently represents an aromatic ring which may have a substituent, and in one embodiment, is preferably a benzene ring which may have a substituent, more preferably a benzene ring which may be substituted with an alkyl group, and further preferably an (unsubstituted) benzene ring.
[0124] m represents an integer of 1 or greater, preferably an integer of 1-20.
[0125] The maleimide resin having an indane skeleton can be produced using, for example, the method described in Japan Invention Association Publication Technical Bulletin No. 2020-500211 or a method based thereon.
[0126] The maleimide equivalent of the (A) maleimide resin is preferably 50 g / eq. or more, more preferably 100 g / eq. or more, further preferably 150 g / eq. or more, further more preferably 200 g / eq. or more, further more preferably 250 g / eq. or more, particularly preferably 300 g / eq. or more, and the upper limit is preferably 2000 g / eq. or less, more preferably 1000 g / eq. or less, further more preferably 800 g / eq. or less, further more preferably 600 g / eq. or less, further more preferably 500 g / eq. or less, particularly preferably 450 g / eq. or less. The maleimide equivalent is the mass of the (A) maleimide resin per 1 molar equivalent of maleimide groups.
[0127] The molecular weight of the (A) maleimide resin is preferably less than 5000, more preferably less than 3000, further preferably less than 2000, further preferably less than 1500, further preferably less than 1200, particularly preferably less than 1000. The lower limit is not particularly limited, and may be, for example, 300 or more, 400 or more, 500 or more, etc.
[0128] When all non-volatile components in the resin composition are set to 100% by mass, the content of the (A) maleimide resin in the resin composition is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 0.5% by mass or more, further preferably 1% by mass or more, particularly preferably 2% by mass or more, and the upper limit is preferably 99% by mass or less, more preferably 90% by mass or less, further preferably 70% by mass or less, further preferably 50% by mass or less, further preferably 40% by mass or less, particularly preferably 35% by mass or less.
[0129] When (C) inorganic filler is included, the content of (A) maleimide resin when the non-volatile components other than (C) inorganic filler in the resin composition are set to 100% by mass is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 1% by mass or more, further preferably 5% by mass or more, particularly preferably 8% by mass or more, and the upper limit is preferably 99.9% by mass or less, particularly preferably 99.5% by mass or less.
[0130] <(B) Acid Salt of Amine Compound Represented by Formula (I)>
[0131] The resin composition of the present invention comprises (B) an acid salt of an amine compound represented by formula (I),
[0132] [Chemistry 9]
[0133]
[0134] [Where R1 , R 2 , R 3 , R 4 and R 5
[0047] The acid salt of the amine compound represented by formula (I) (B) has a function as a maleimide resin curing catalyst that promotes the curing of the maleimide resin. In addition, when the resin composition contains an epoxy resin, the acid salt of the amine compound represented by formula (I) (B) also has a function as an epoxy resin curing catalyst that promotes the curing of the epoxy resin. The acid salt of the amine compound represented by formula (I) (B) may be used alone or in combination of two or more.
[0135] As R 1 , R 2 , R 3 , R 4 and R 5 The "substituent" in the formula is not particularly limited, and examples thereof include a halogen atom, a heteroaryl group, -CN, -NO2, -OH, -SH, -NH2, -CHO, -R sl 、-OR s1 、-NHR s1 、-N(R s1 2. -COR s1 、-COOR s1 、-OCOR s1 ,-CONHR s1 、-NHCOR s1 、-SR s1 、-SO2R s1 etc. monovalent substituents (herein, R s1 Each independently represents a halogen atom, a heteroaryl group, -CN, -NO2, -OH, -SH, -NH2, -CHO, -OR s2 、-NHR s2 、-N(R s2 2. -COR s2 、-COOR s2 、-OCOR s2 ,-CONHR s2 、-NHCOR s2 、-SR s2 、-SO2R s2 A monovalent hydrocarbon group substituted with a substituent such as s2 each independently represents a monovalent hydrocarbon group).
[0136] Heteroaryl refers to a monovalent group formed by removing one hydrogen atom from an aromatic heterocyclic ring having heteroatoms such as oxygen atoms, nitrogen atoms, and sulfur atoms as ring atoms in addition to carbon atoms. Unless otherwise specified, the heteroaryl is preferably a 5- to 14-membered heteroaryl, and particularly preferably a 5- to 10-membered heteroaryl. Examples of the heteroaryl include furyl, thienyl, pyrrolyl, pyrazolyl, oxazolyl, isoxazolyl, thiazolyl, imidazolyl, pyridyl, pyridazinyl, pyrimidinyl, pyrazinyl, and triazinyl.
[0137] R 1 and R 5 Each independently represents a hydrogen atom or a substituent, and in one embodiment, preferably a hydrogen atom, -OH, -SH, -NH2, -OR s1 、-NHR s1 、-N(R s1 2. -OCOR s1 、-NHCORs 1 , or -SRs 1 (R s1 Same as above), particularly preferably a hydrogen atom.
[0138] R 2 and R 4 Each independently represents a hydrogen atom or a substituent, and in one embodiment, a hydrogen atom is particularly preferred.
[0139] R 3 represents a hydrogen atom or a substituent, and in one embodiment, is preferably a substituent, more preferably -OH, -SH, -NH2, -OR s1 、-NHR s1 、-N(R s1 2. -OCOR s1 、-NHCOR s1 , or -SR s1 (R s1 Same as above), further preferably -N(R s1 )2(R s1 Same as above), particularly preferably N,N-dimethylamino.
[0140] The molecular weight of the amine compound represented by formula (I) is not particularly limited, and is, for example, 4000 or less, 3000 or less, 2000 or less, preferably 1000 or less, more preferably 700 or less, further preferably 500 or less, further preferably 300 or less, further preferably 200 or less, and particularly preferably 150 or less.
[0141] Specific examples of the amine compound represented by formula (I) include pyridine, 2-aminopyridine, 3-aminopyridine, 4-aminopyridine, 2-dimethylaminopyridine, 4-dimethylaminopyridine, 2-diethylaminopyridine, 4-diethylaminopyridine, 2-(aminomethyl)pyridine, 2-amino-3-methylpyridine, 2-amino-4-methylpyridine, 2-amino-5-methylpyridine, 2-amino-6-methylpyridine, 3-(2-aminoethyl)pyridine, 4-(2-aminoethyl)pyridine, 2-methoxypyridine, 4-methoxypyridine, 2-ethoxypyridine, 4-ethoxypyridine, 2-hydroxypyridine, and 4-hydroxypyridine. Among them, 4-dimethylaminopyridine (hereinafter sometimes referred to as "DMAP") is preferred.
[0142] In one embodiment, the acid salt of the amine compound represented by formula (I) preferably comprises a salt of the amine compound represented by formula (I) and an organic acid selected from carboxylic acids (including aliphatic carboxylic acids and aromatic carboxylic acids) and sulfonic acids (including aliphatic sulfonic acids and aromatic sulfonic acids); more preferably comprises a salt of the amine compound represented by formula (I) and an organic acid represented by any one of formulas (IIa) to (IIc),
[0143] [Chemistry 10]
[0144]
[0145] [Wherein,
[0146] X represents -CO- or -SO2-,
[0147] R a , R b , R c , R d , R e , R f and R g each independently represents a hydrogen atom or a substituent].
[0148] As R a , R b , R c , R d , R e , R f and R g The "substituent" in the formula is not particularly limited, and examples thereof include a halogen atom, a heteroaryl group, -CN, -NO2, -OH, -SH, -CHO, -COOH, -SO3H, -R t1 、-OR t1 、-COR t1 、-COOR t1 ,OCOR t1 ,-CONHR t1 、-NHCORt1 、-SR t1 、-SO2R t1 etc. monovalent substituents (herein, R t1 Each independently represents a halogen atom, a heteroaryl group, -CN, -NO2, -OH, -SH, -CHO, -COOH, -SO3H, -OR t2 、-COR t2 、-COOR t2 、-OCOR t2 ,-CONHR t2 、-NHCOR t2 、-SR t2 、-SO2R t2 A monovalent hydrocarbon group substituted with an equal substituent; R t2 each independently represents a monovalent hydrocarbon group).
[0149] R a , R b , R c , R d , R e , R f and R g Each independently represents a hydrogen atom or a substituent, and in one embodiment, preferably a hydrogen atom, -COOH, -SO3H, or -R t1 , more preferably a hydrogen atom, a methyl group, -COOH, or -SO3H.
[0150] The molecular weight of the organic acid represented by any of the formulae (IIa) to (IIc) is not particularly limited, and is, for example, 4000 or less, 3000 or less, or 2000 or less, preferably 1000 or less, more preferably 700 or less, further preferably 500 or less, further preferably 400 or less, further preferably 300 or less, and particularly preferably 250 or less.
[0151] Specific examples of the organic acid represented by any one of the formulae (IIa) to (IIc) include benzoic acid (pK a =4.2), o-toluic acid (pK a =3.9), m-toluic acid (pK a =4.3), p-toluic acid (pK a =4.4), 2-ethylbenzoic acid (pK a =3.8), 3-ethylbenzoic acid (pK a =4.3), 4-ethylbenzoic acid (pK a =4.4), 2-isopropylbenzoic acid (pK a =3.6), 2-tert-butylbenzoic acid (pK a=3.5), 2,3-dimethylbenzoic acid (pK a =3.8), 2,4-dimethylbenzoic acid (pK a =4.2), 2,5-dimethylbenzoic acid (pK a =4.0), 2,6-dimethylbenzoic acid (pK a =3.4), 3,5-dimethylbenzoic acid (pK a =4.3), 2,4,6-trimethylbenzoic acid (pK a =3.4), 2,4,6-triisopropylbenzoic acid (pK a =3.2), o-methoxybenzoic acid (pK a =4.1), m-methoxybenzoic acid (pK a =4.1), p-methoxybenzoic acid (pK a =4.5), 2,6-dimethoxybenzoic acid (pK a =3.4), 2-ethoxybenzoic acid (pK a =4.2), 2-acetylaminobenzoic acid (pK a =3.6), 2-acetoxybenzoic acid (pK a =4.6), 2-acetylbenzoic acid (pK a =4.1), 3-acetylbenzoic acid (pK a =3.8), 2-phenylbenzoic acid (pK a =3.5), 3-phenylbenzoic acid (pK a =4.1), 4-phenylbenzoic acid (pK a =4.2), 2-phenoxybenzoic acid (pK a =3.5), 2-benzoylbenzoic acid (pK a =3.5), 2-fluorobenzoic acid (pK a =3.3), 3-fluorobenzoic acid (pK a =3.9), 4-fluorobenzoic acid (pK a =4.2), pentafluorobenzoic acid (pK a =1.8), 2-chlorobenzoic acid (pK a =2.9), 2,4-dichlorobenzoic acid (pK a =2.7), 2,5-dichlorobenzoic acid (pK a =2.5), 2,6-dichlorobenzoic acid (pK a =1.6), 2-bromobenzoic acid (pK a =2.8), 2-nitrobenzoic acid (pK a =2.2), 3-nitrobenzoic acid (pK a =3.5), 4-nitrobenzoic acid (pK a=3.4), 2-cyanobenzoic acid (pK a =3.1), 2-hydroxybenzoic acid (pK a =3.0), 4-(trifluoromethyl)benzoic acid (pK a =3.7), 2,6-bis(trifluoromethyl)benzoic acid (pK a =2.3), 1-naphthoic acid (pK a =3.7), 2-naphthoic acid (pK a =4.2) and other aromatic monocarboxylic acids; phthalic acid (pK a1 =2.9), isophthalic acid (pK a1 =3.5), terephthalic acid (pK a1 =3.5), 4-methylphthalic acid (pK a1 =3.3), 5-methylisophthalic acid (pK a1 =3.6), 5-methylterephthalic acid (pK a1 =3.4), 3-methoxyphthalic acid (pK a1 =3.1), 4-methoxyphthalic acid (pK a1 =3.1), 3-fluorophthalic acid (pK a1 =2.3), 4-fluorophthalic acid (pK a1 =2.9), tetrafluorophthalic acid (pK a1 =1.3), 1,4-naphthalene dicarboxylic acid (pK a1 =2.7), 2,3-naphthalene dicarboxylic acid (pK a1 =3.0), 2,6-naphthalene dicarboxylic acid (pK a1 =3.7), 2,7-naphthalene dicarboxylic acid (pK a1 =3.7), trimesic acid (pK a1 =2.9), trimellitic acid (pK a1 =2.5), trimesic acid (pK a1 =3.1), pyromellitic acid (pK a1 =1.9) and other aromatic polycarboxylic acids, benzenesulfonic acid (pK a =-2.8), p-toluenesulfonic acid (pK a =-2.8), p-xylene-2-sulfonic acid (pK a =-0.5), naphthalenesulfonic acid (pK a =0.3) and other aromatic monosulfonic acids, 1,3-benzenedisulfonic acid (pK a1 =-1.4), 1,2-benzenedisulfonic acid (pK a1 =-1.1), 1,3,5-benzenetrisulfonic acid (pK a1=-2.1) and the like, among which an organic acid selected from phthalic acid, trimellitic acid and p-toluenesulfonic acid is preferred.
[0152] In one embodiment, the acid salt of the amine compound represented by formula (I) preferably comprises an acid dissociation constant (pK) of the amine compound represented by formula (I) with water at 25°C. a ) is 4.5 or less (preferably a carboxylic acid or a sulfonic acid, particularly preferably an organic acid represented by any one of the formulas (IIa) to (IIc)); more preferably, an amine compound represented by formula (I) has an acid dissociation constant (pK a ) is 4.0 or less (preferably a carboxylic acid or a sulfonic acid, and particularly preferably an organic acid represented by any one of the formulas (IIa) to (IIc)); further preferably, an amine compound represented by formula (I) with an acid dissociation constant (pK a ) is 3.5 or less (preferably a carboxylic acid or a sulfonic acid, and particularly preferably an organic acid represented by any one of the formulas (IIa) to (IIc)); further preferably, an amine compound represented by formula (I) with an acid dissociation constant (pK a ) is 3.0 or less (preferably a carboxylic acid or a sulfonic acid, and particularly preferably an organic acid represented by any of the formulae (IIa) to (IIc)). Here, in the case of a polybasic organic acid, the acid dissociation constant refers to the lowest acid dissociation constant (pK a1 ).
[0153] When all non-volatile components in the resin composition are set to 100% by mass, the content of the acid salt of the amine compound (B) represented by formula (I) in the resin composition is preferably 0.0001% by mass or more, more preferably 0.001% by mass or more, further preferably 0.01% by mass or more, further preferably 0.05% by mass or more, particularly preferably 0.1% by mass or more, and the upper limit is preferably 10% by mass or less, more preferably 5% by mass or less, further preferably 3% by mass or less, further preferably 2% by mass or less, further preferably 1% by mass or less, particularly preferably 0.5% by mass or less.
[0154] When (C) inorganic filler is included, the content of the acid salt of the amine compound (B) represented by formula (I) when the non-volatile components other than the (C) inorganic filler in the resin composition are set to 100% by mass is preferably 0.0001% by mass or more, more preferably 0.001% by mass or more, further preferably 0.01% by mass or more, further preferably 0.1% by mass or more, particularly preferably 0.5% by mass or more, and the upper limit is preferably 10% by mass or less, more preferably 5% by mass or less, further preferably 3% by mass or less, further preferably 2% by mass or less, particularly preferably 1% by mass or less.
[0155] The mass ratio of the acid salt of the amine compound represented by formula (I) (B) to the maleimide resin (A) in the resin composition (content of component (B) / content of component (A)) is preferably 0.00001 or more, more preferably 0.0001 or more, further preferably 0.001 or more, particularly preferably 0.005 or more, and the upper limit is preferably 0.3 or less, more preferably 0.2 or less, further preferably 0.15 or less, particularly preferably 0.1 or less.
[0156] <(C) Inorganic filler>
[0157] The resin composition of the present invention may further contain (C) an inorganic filler as an optional component. The (C) inorganic filler is contained in the resin composition in the form of particles.
[0158] As the material of (C) inorganic filler, an inorganic compound is used. As the example of the material of (C) inorganic filler, for example, silica, alumina, aluminosilicate, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, zirconium phosphate and zirconium tungstate phosphate, etc., can be listed. Among them, silica, alumina or aluminosilicate is preferred, and silica is particularly preferred. As silica, for example, amorphous silica, fused silica, crystalline silica, synthetic silica, hollow silica, etc. can be listed. In addition, as silica, spherical silica is preferred. (C) The inorganic filler may be used alone or in combination of two or more at any ratio.
[0159] (C) Commercially available products of the inorganic filler include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical Materials Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Yaduma Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by DENKA Corporation; "SILFIL NSS-3N", "SILFIL NSS-4N", and "SILFIL NSS-5N" manufactured by Tokuyama Corporation; "Selfies" and "MGH-005" manufactured by Pacific Cement Co., Ltd.; and "HIPRESICA FH" manufactured by Ube Exsymo Corporation.
[0160] (C) The average particle size of the inorganic filler is not particularly limited, preferably less than 10 μm, more preferably less than 5 μm, further preferably less than 3 μm, further preferably less than 1 μm, and particularly preferably less than 0.8 μm. (C) The lower limit of the average particle size of the inorganic filler is not particularly limited, preferably more than 0.01 μm, more preferably more than 0.05 μm, further preferably more than 0.1 μm, and particularly preferably more than 0.2 μm. (C) The average particle size of the inorganic filler can be measured by a laser diffraction scattering method based on Mie scattering theory. Specifically, a particle size distribution of an inorganic filler can be prepared on a volume basis by a laser diffraction scattering particle size distribution measuring device, and the median particle size can be measured as the average particle size. The sample can be measured by weighing 100 mg of an inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. For the measurement sample, a laser diffraction particle size distribution measuring device is used, and the wavelength of the light source is set to blue and red, and the volume-based particle size distribution of the inorganic filler is measured in a flow cell manner, and the average particle size is calculated as the median particle size according to the obtained particle size distribution. As a laser diffraction particle size distribution measuring device, for example, "LA-960" made by Horiba Manufacturing Co., Ltd. can be cited.
[0161] (C) The specific surface area of the inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 The upper limit of the specific surface area of the inorganic filler (C) is not particularly limited, but is preferably 100 m 2 / g or less, preferably 50m 2 / g or less, more preferably 30m 2 / g or less, particularly preferably 10m2 The specific surface area of the inorganic filler can be obtained by adsorbing nitrogen gas on the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech) according to the BET method and calculating the specific surface area by the BET multipoint method.
[0162] (C) The inorganic filler may be a solid inorganic filler having an average porosity of 0 volume % (preferably solid silica, solid alumina, solid aluminosilicate), or a hollow inorganic filler having an average porosity exceeding 0 volume % (preferably hollow silica, hollow alumina, hollow aluminosilicate).
[0163] From the viewpoint of improving moisture resistance and dispersibility, (C) inorganic filler is preferably treated with a surface treatment agent. As the surface treatment agent, for example, fluorine-containing silane coupling agent, aminosilane coupling agent, epoxysilane coupling agent, mercaptosilane coupling agent, silane coupling agent, alkoxysilane, organosilazane compound, titanate coupling agent, etc. can be listed. In addition, the surface treatment agent can be used alone or in any combination of two or more.
[0164] Commercially available products of the surface treatment agent include, for example, “KBM403” (3-glycidoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM803” (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM903” (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM573” (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “SZ-31” (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM103” (phenyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM-4803” (long-chain epoxy-type silane coupling agent) manufactured by Shin-Etsu Chemical Co., Ltd., and “KBM-7103” (3,3,3-trifluoropropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd.
[0165] From the viewpoint that the dispersibility of inorganic filler improves, the degree of surface treatment performed by surface treatment agent is preferably controlled within a specified range. Specifically, 100% by mass of inorganic filler is preferably surface treated with a surface treatment agent of 0.2% by mass to 5% by mass, more preferably with a surface treatment agent of 0.2% by mass to 3% by mass, and further preferably with a surface treatment agent of 0.3% by mass to 2% by mass.
[0166] The degree of surface treatment by the surface treatment agent can be evaluated by the carbon content per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the carbon content per unit surface area of the inorganic filler is preferably 0.02 mg / m2 More than 0.1 mg / m 2 More preferably, 0.2 mg / m 2 On the other hand, from the viewpoint of preventing the increase of the melt viscosity of the resin composition and the melt viscosity in the form of a sheet, the carbon content per unit surface area of the inorganic filler is preferably 1.0 mg / m 2 Below, preferably 0.8mg / m 2 Below, more preferably 0.5 mg / m 2 the following.
[0167] (C) The amount of carbon per unit surface area of the inorganic filler can be measured after the surface-treated inorganic filler is cleaned with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK is added as a solvent to the inorganic filler surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid component, a carbon analyzer can be used to measure the amount of carbon per unit surface area of the inorganic filler. As a carbon analyzer, the "EMIA-320V" manufactured by Horiba, Ltd. can be used.
[0168] When all non-volatile components in the resin composition are set to 100% by mass, the content of the (C) inorganic filler in the resin composition is, for example, 0% by mass or more, preferably 0.1% by mass or more, more preferably 1% by mass or more, further preferably 10% by mass or more, further preferably 20% by mass or more, further preferably 30% by mass or more, particularly preferably 40% by mass or more, and the upper limit is preferably 95% by mass or less, more preferably 90% by mass or less, further preferably 85% by mass or less, particularly preferably 80% by mass or less.
[0169] The mass ratio of the (C) inorganic filler to the (A) maleimide resin in the resin composition (component (C) / component (A)) is not particularly limited, and is, for example, 0 or more, preferably 0.1 or more, more preferably 0.3 or more, further preferably 0.5 or more, further preferably 0.7 or more, further preferably 1.0 or more, particularly preferably 1.3 or more, and the upper limit is preferably 200 or less, more preferably 100 or less, further preferably 50 or less, particularly preferably 30 or less.
[0170] When all non-volatile components in the resin composition are set to 100% by mass, the total content of (A) maleimide resin, (B) acid salt of amine compound represented by formula (I) and (C) inorganic filler in the resin composition is, for example, 5% by mass or more, 10% by mass or more, preferably 30% by mass or more, more preferably 50% by mass or more, further preferably 60% by mass or more, further preferably 70% by mass or more, and particularly preferably 74% by mass or more.
[0171] <(D) Anionic polymerizable curing agent>
[0172] The resin composition of the present invention may further contain (D) anionic polymerizable curing agent as an optional component. (D) Anionic polymerizable curing agent may have the function of anionically reacting with maleimide resin, epoxy resin, etc. to cure them. (D) Anionic polymerizable curing agent may be used alone or in any combination of two or more.
[0173] Examples of the anionic polymerizable curing agent (D) include phenolic curing agents, carbodiimide curing agents, amine curing agents, benzoxazine curing agents, and active ester curing agents. Among them, the anionic polymerizable curing agent (D) preferably includes a phenolic curing agent.
[0174] As phenolic curing agent, it is possible to use a curing agent having more than one, preferably more than two hydroxyls (phenolic hydroxyls) combined with aromatic rings such as benzene rings and naphthalene rings in one molecule. As phenolic curing agent, for example, a phenolic curing agent with a polyphenylene ether structure, a phenolic curing agent with a biphenyl structure (especially a curing agent containing 1-propylene), a phenolic curing agent with a phenolic structure (especially a curing agent containing a triazine skeleton) etc. can be listed. These curing agents can be used alone or in combination of two or more.
[0175] Commercially available products of phenolic curing agents include, for example, "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Chemicals; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-375", and "SN-395" manufactured by Nippon Steel Chemicals; "LA-7052", "LA-7054", "LA-3018", "LA-3018-50P", "LA-1356", "TD-2090", "TD-2090-60M", and "KA-1160" manufactured by DIC; and "SA90" manufactured by SABIC. These curing agents may be used alone or in combination of two or more.
[0176] Examples of the carbodiimide curing agent include curing agents having one or more, preferably two or more, carbodiimide structures in one molecule, such as aliphatic biscarbodiimides such as tetramethylene-bis(tert-butylcarbodiimide) and cyclohexanebis(methylene-tert-butylcarbodiimide); biscarbodiimides such as aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide) and poly(isophoronecarbodiimide); imide; poly(phenylene carbodiimide), poly(naphthylene carbodiimide), poly(tolylene carbodiimide), poly(methyl diisopropyl phenylene carbodiimide), poly(triethyl phenylene carbodiimide), poly(diethyl phenylene carbodiimide), poly(triisopropyl phenylene carbodiimide), poly(diisopropyl phenylene carbodiimide), poly(xylylene carbodiimide), poly(tetramethyl xylylene carbodiimide), poly(methylene diphenylene carbodiimide), poly[methylene bis(methyl phenylene) carbodiimide] and the like aromatic polycarbodiimides and the like. These curing agents may be used alone or in combination of two or more.
[0177] Commercially available products of carbodiimide curing agents include, for example, "CARBODILITE V-02B", "CARBODILITE V-03", "CARBODILITE V-04K", "CARBODILITE V-07", and "CARBODILITE V-09" manufactured by Nisshinbo Chemical Co., Ltd., and "Stabaxol P", "Stabaxol P400", and "Hycasyl 510" manufactured by LANXESS Co., Ltd. These curing agents may be used alone or in combination of two or more.
[0178] As the amine curing agent, there can be mentioned curing agents having one or more, preferably two or more amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc. Among them, aromatic amines are preferred from the viewpoint of exerting the desired effect of the present invention. The amine curing agent is preferably a primary amine or a secondary amine, more preferably a primary amine.
[0179] Specific examples of amine curing agents include 4,4′-methylenebis(2,6-dimethylaniline), 4,4′-diaminodiphenylmethane, 4,4′-diaminodiphenyl sulfone, 3,3′-diaminodiphenyl sulfone, metaphenylenediamine, metaxylylenediamine, diethyltoluenediamine, 4,4′-diaminodiphenyl ether, 3,3′-dimethyl-4,4′-diaminobiphenyl, 2,2′-dimethyl-4,4′-diaminobiphenyl, 3,3′-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxy bis(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone and the like. Amine curing agents can be commercially available products; examples thereof include "SEIKACURE-S" manufactured by Seika Corporation; "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", "KAYAHARDA-S" manufactured by Nippon Kayaku Co., Ltd.; "EPICURE W" manufactured by Mitsubishi Chemical Corporation; "DTDA" manufactured by Sumitomo Seika Chemicals Co., Ltd.; "WA" manufactured by DIC Corporation, etc. These curing agents may be used alone or in combination of two or more.
[0180] Examples of the benzoxazine curing agent include those having one or more, preferably two or more, benzoxazine structures in one molecule.
[0181] Commercially available products of benzoxazine curing agents include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Industry Co., Ltd., "HFB2006M" manufactured by Showa High Molecular Co., Ltd., and "Pd", "Fa", and "ALP-d" manufactured by Shikoku Chemical Industry Co., Ltd. These curing agents may be used alone or in combination of two or more.
[0182] As active ester curing agent, generally preferably use phenol esters, thiophenol esters, N-hydroxylamine esters, heterocyclic hydroxy compounds and other esters with more than two reactive ester groups in one molecule. The active ester compound is preferably a compound obtained by the condensation reaction of a carboxylic acid compound and / or a thiocarboxylic acid compound with a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improved heat resistance, the active ester curing agent is preferably an active ester compound obtained from a carboxylic acid compound and a hydroxy compound, and more preferably an active ester compound obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound. As the carboxylic acid compound, for example, benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, etc. can be cited. Examples of the phenol compound or naphthol compound include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the "dicyclopentadiene-type diphenol compound" refers to a diphenol compound obtained by condensing two molecules of phenol with one molecule of dicyclopentadiene.
[0183] Specifically, the active ester curing agent is preferably a dicyclopentadiene type active ester compound, a naphthalene type active ester compound containing a naphthalene structure, an active ester compound containing an acetylated product of a phenol novolac resin, or an active ester compound containing a benzoylated product of a phenol novolac resin, and more preferably at least one selected from a dicyclopentadiene type active ester compound and a naphthalene type active ester compound. As the dicyclopentadiene type active ester compound, an active ester compound containing a dicyclopentadiene type diphenol structure is preferred.
[0184] As commercially available active ester curing agents, active ester compounds containing a dicyclopentadiene-type diphenol structure include "EXB9451", "EXB9460", "EXB9460S", "HPC-8000L-65TM", "HPC-8000-65T", "HPC-8000H", and "HPC-8000H-65TM" (manufactured by DIC Corporation); active ester compounds containing a naphthalene structure include "HP-B-8151-62T", "EXB-8100L-65T", "EXB-9416-7 Examples of the active ester compounds include "EXB-0BK", "HPC-8150-62T", and "EXB-8" (manufactured by DIC Corporation); examples of phosphorus-containing active ester compounds include "EXB9401" (manufactured by DIC Corporation), examples of active ester compounds of acetylated phenol novolac resins include "DC808" (manufactured by Mitsubishi Chemical Corporation), examples of active ester compounds of benzoylated phenol novolac resins include "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and examples of active ester compounds containing vinylphenyl and naphthalene structures include "PC1 300-02-65MA" (manufactured by AIR&WATER Corporation), etc.
[0185] The reactive group equivalent of the (D) anionic polymerizable curing agent is preferably 3000 g / eq. or less, more preferably 2000 g / eq. or less, further preferably 1000 g / eq. or less, particularly preferably 800 g / eq. or less, and its lower limit is preferably 40 g / eq. or more, more preferably 60 g / eq. or more, further preferably 80 g / eq. or more, particularly preferably 100 g / eq. or more. The reactive group equivalent is the mass of the (D) anionic polymerizable curing agent per 1 molar equivalent of reactive groups. The reactive group refers to a functional group that reacts anionically with a maleimide resin, an epoxy resin, etc. For example, if it is a phenolic curing agent, it refers to a phenolic hydroxyl group, if it is a carbodiimide curing agent, it refers to a carbodiimide group (-N=C=N-), if it is an amine curing agent, it refers to an amino group, if it is a benzoxazine curing agent, it refers to a benzoxazine group, and if it is an active ester curing agent, it refers to a reactive ester group (ester of phenolic hydroxyl group).
[0186] When all non-volatile components in the resin composition are set to 100% by mass, the content of the anionic polymerizable curing agent (D) in the resin composition is, for example, 0% by mass or more, preferably 0.01% by mass or more, better 0.1% by mass or more, further better 0.5% by mass or more, further better 0.8% by mass or more, particularly better 1% by mass or more, and the upper limit is preferably 50% by mass or less, better 40% by mass or less, further better 30% by mass or less, further better 25% by mass or less, further better 20% by mass or less, particularly better 15% by mass or less.
[0187] When (C) inorganic filler is included, the content of (D) anionic polymerizable curing agent when the non-volatile components other than (C) inorganic filler in the resin composition are set to 100% by mass is, for example, 0% by mass or more, preferably 0.01% by mass or more, better 0.1% by mass or more, further better 0.5% by mass or more, further better 1% by mass or more, particularly better 3% by mass or more, and the upper limit is preferably 90% by mass or less, better 80% by mass or less, further better 70% by mass or less, further better 60% by mass or less, particularly better 50% by mass or less.
[0188] The mass ratio of the anionic polymerizable curing agent (D) to the maleimide resin (A) in the resin composition (content of the component (D) / content of the component (A)) is, for example, 0 or more, preferably 0.001 or more, more preferably 0.01 or more, further preferably 0.03 or more, particularly preferably 0.05 or more, and the upper limit is preferably 20 or less, more preferably 10 or less, further preferably 7 or less, particularly preferably 5 or less.
[0189] <(E) Epoxy resin>
[0190] The resin composition of the present invention may further contain (E) an epoxy resin as an optional component. (E) The epoxy resin is a curable resin having an epoxy group and an epoxy equivalent of 5000 g / eq. or less.
[0191] Examples of the epoxy resin (E) include biphenylol epoxy resins, bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, bisphenol AF epoxy resins, dicyclopentadiene epoxy resins, trisphenol epoxy resins, naphthol novolac epoxy resins, phenol novolac epoxy resins, tert-butyl-catechol epoxy resins, naphthalene epoxy resins, naphthol epoxy resins, anthracene epoxy resins, glycidylamine epoxy resins, glycidylester epoxy resins. The epoxy resins include cresol novolac type epoxy resins, phenol aralkyl type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexanedimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, isocyanurate type epoxy resins, phenol phthalimidine type epoxy resins, etc. (E) The epoxy resins may be used alone or in combination of two or more.
[0192] The resin composition of the present invention preferably contains an epoxy resin having two or more epoxy groups in one molecule as the epoxy resin (E). Relative to 100% by mass of the epoxy resin (E), the proportion of the epoxy resin having two or more epoxy groups in one molecule is preferably 50% by mass or more, more preferably 60% by mass or more, particularly preferably 70% by mass or more, and usually 100% by mass or less.
[0193] (E) Epoxy resins include epoxy resins that are liquid at 20°C (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at 20°C (hereinafter sometimes referred to as "solid epoxy resins"). In the resin composition of the present invention, the epoxy resin may include only a liquid epoxy resin, only a solid epoxy resin, or both a liquid epoxy resin and a solid epoxy resin, but it is particularly preferred to include both a liquid epoxy resin and a solid epoxy resin.
[0194] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.
[0195] As liquid epoxy resins, preferred are glycyrrhizin type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins having an ester skeleton, cyclohexanedimethanol type epoxy resins, cyclic aliphatic glycidyl ethers, and epoxy resins having a butadiene structure.
[0196] Specific examples of liquid epoxy resins include "EX-992L" manufactured by Nagase ChemteX, "YX7400" manufactured by Mitsubishi Chemical Corporation; "HP4032", "HP4032D", "HP4032SS" (naphthalene-type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "828EL", "825", "EPIKOTE "828EL" (bisphenol A type epoxy resin); "hER807", "1750" (bisphenol F type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630", "630LSD", "604" (glycidylamine type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "ED-523T" (licorice phenol type epoxy resin) manufactured by ADEKA Corporation; "EP-3950L", "EP-3980S" (glycidylamine type epoxy resin) manufactured by ADEKA Corporation; "EP-4088S" (dicyclopentadiene type epoxy resin) manufactured by ADEKA Corporation; "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical Materials Co., Ltd.; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX Corporation; "EX-991L" manufactured by ChemteX (an epoxy resin containing an alkylene oxide skeleton and a butadiene skeleton); "CELLOXIDE2021P" manufactured by Daicel Corporation (an alicyclic epoxy resin having an ester skeleton); "PB-3600" manufactured by Daicel Corporation, "JP-100" and "JP-200" manufactured by Nippon Soda Co., Ltd. (epoxy resins having a butadiene structure); "ZX1 658" and "ZX1658GS" manufactured by Nippon Steel Chemical Materials Co., Ltd. (liquid 1,4-glycidylcyclohexane type epoxy resins); "EG-280" manufactured by Osaka Gas Chemical Co., Ltd. (an epoxy resin containing a fluorene structure); "EX-201" manufactured by Nagase ChemteX Co., Ltd. (cyclic aliphatic glycidyl ether), etc.
[0197] The solid epoxy resin is preferably a solid epoxy resin having three or more epoxy groups in one molecule, more preferably an aromatic solid epoxy resin having three or more epoxy groups in one molecule.
[0198] As solid epoxy resins, preferred are biphenylol type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, naphthol novolac type epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, phenol aralkyl type epoxy resins, tetraphenylethane type epoxy resins, and phenol benzopyrrolidone type epoxy resins.
[0199] Specific examples of solid epoxy resins include "HP4032H" (naphthalene-type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resin) manufactured by DIC Corporation; "N-690" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene-type epoxy resin) manufactured by DIC Corporation; resin); "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000", "HP6000L" (naphthylene ether type epoxy resin) manufactured by DIC Corporation; "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol phenolic type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000L", "N C3000FH", "NC3100" (biphenyl type epoxy resin); "ESN475V", "ESN4100V" (naphthalene type epoxy resin) manufactured by Nippon Steel Chemicals; "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemicals; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemicals; "YX4000H", "YX4000", "YX4000HK", "YL7890" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "Y L6121" (biphenyl type epoxy resin); "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YX7700" (phenol aralkyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1 031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "WHR991S" (phenol benzopyrrolidone type epoxy resin) manufactured by Nippon Kayaku Co., Ltd., etc. These resins may be used alone or in combination of two or more.
[0200] When a liquid epoxy resin and a solid epoxy resin are used in combination as the epoxy resin (E), the mass ratio thereof (liquid epoxy resin:solid epoxy resin) is preferably from 10:1 to 1:50, more preferably from 5:1 to 1:20, further preferably from 2:1 to 1:10, particularly preferably from 1:1 to 1:3.
[0201] (E) The epoxy equivalent of the epoxy resin is preferably 50 g / eq. to 5000 g / eq., more preferably 60 g / eq. to 2000 g / eq., further preferably 70 g / eq. to 1000 g / eq., and further preferably 80 g / eq. to 500 g / eq. The epoxy equivalent is the mass of the resin per 1 equivalent of epoxy group. The epoxy equivalent can be measured according to JIS K7236.
[0202] (E) The weight average molecular weight (Mw) of the epoxy resin is preferably from 100 to 5000, more preferably from 250 to 3000, further preferably from 400 to 1500. The weight average molecular weight of the resin can be measured as a value calculated in terms of polystyrene by gel permeation chromatography (GPC).
[0203] When all non-volatile components in the resin composition are set to 100% by mass, the content of the (E) epoxy resin in the resin composition is, for example, 0% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 0.5% by mass or more, further more preferably 1% by mass or more, particularly preferably 2% by mass or more, and the upper limit is preferably 50% by mass or less, more preferably 40% by mass or less, further more preferably 30% by mass or less, further more preferably 25% by mass or less, further more preferably 20% by mass or less, particularly preferably 15% by mass or less.
[0204] When (C) inorganic filler is included, the content of (E) epoxy resin when the non-volatile components other than (C) inorganic filler in the resin composition are set to 100% by mass is, for example, 0% by mass or more, preferably 0.01% by mass or more, better 0.1% by mass or more, further better 1% by mass or more, further better 3% by mass or more, particularly better 5% by mass or more, and the upper limit is preferably 90% by mass or less, better 75% by mass or less, further better 60% by mass or less, further better 50% by mass or less, particularly better 40% by mass or less.
[0205] The mass ratio of the (E) epoxy resin to the (A) maleimide resin in the resin composition (content of the (E) component / content of the (A) component) is, for example, 0 or more, preferably 0.001 or more, more preferably 0.01 or more, further preferably 0.05 or more, particularly preferably 0.1 or more, and the upper limit is preferably 20 or less, more preferably 10 or less, further preferably 7 or less, particularly preferably 5 or less.
[0206] <(F) Thermoplastic resin>
[0207] The resin composition of the present invention may further contain (F) a thermoplastic resin as an optional component. The (F) thermoplastic resin described here refers to a component other than the (D) anionic polymerizable curing agent and (E) epoxy resin described above.
[0208] As (F) thermoplastic resin, for example, polystyrene resin, resin containing oxazoline group, polyimide resin, phenoxy resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyamide-imide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene oxide resin, polycarbonate resin, polyetheretherketone resin, polyester resin etc. can be listed. In one embodiment, (F) thermoplastic resin preferably comprises a thermoplastic resin selected from polystyrene resin, resin containing oxazoline group, polyimide resin and phenoxy resin, more preferably comprises a thermoplastic resin selected from polyimide resin and phenoxy resin, and particularly preferably comprises phenoxy resin. In addition, thermoplastic resin can be used alone or in combination of two or more.
[0209] The polystyrene resin may be a commercially available product, for example, hydrogenated styrene-based thermoplastic elastomers "H1041", "Tuftec H1043", "Tuftec P2000", "Tuftec MP10" (manufactured by Asahi Kasei Corporation), epoxidized styrene-butadiene thermoplastic elastomers "EPOFRIEND AT501", "CT310" (manufactured by Daicel Corporation); modified styrene-based elastomers "SEPTON HG252" (manufactured by Kuraray Co., Ltd.) having a hydroxyl group; modified styrene-based elastomers "Tuftec N503M" having carboxyl groups; modified styrene-based elastomers "Tuftec N501" having amino groups, modified styrene-based elastomers "Tuftec M1913" having acid anhydride groups (manufactured by Asahi Kasei Corporation); unmodified styrene-based elastomers "SEPTON S8104" (manufactured by Kuraray Co., Ltd.), etc.
[0210] The oxazoline group-containing resin is prepared by, for example, mixing 2-isopropenyl-2-oxazoline, 5-methyl-2-isopropenyl-2-oxazoline, 4,4-dimethyl-2-isopropenyl-2-oxazoline, 4-methyl-2-isopropenyl-2-oxazoline, 4,4,5-trimethyl-2-isopropenyl-2-oxazoline, 2-vinyl-2-oxazoline, 5-methyl-2-vinyl-2-oxazoline, 4,4-dimethyl-2-vinyl-2-oxazoline, 4-methyl-2-vinyl-2-oxazoline, 4,4,5-trimethyl-2-vinyl-2-oxazoline and other addition polymerizable oxazoline compounds (monomers containing vinyl oxazoline skeletons) are polymerized, and other monomers such as styrene monomers such as styrene, α-methylstyrene, 4-methylstyrene, 3-methylstyrene, 2-methylstyrene, 4-ethylstyrene, 4-tert-butylstyrene, p-divinylbenzene, and m-divinylbenzene can be copolymerized as needed. As a specific example of the resin containing oxazoline groups, "PX-3-RP-61" made by Japan Catalyst Co., Ltd. can be listed.
[0211] Specific examples of the polyimide resin include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "RIKACOAT SN20" and "RIKACOAT PN20" manufactured by Shin Nippon Chemical Co., Ltd.
[0212] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenol acetophenone skeleton, phenolic skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group selected from the group consisting of a phenolic hydroxyl group and an epoxy group.
[0213] Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (a phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (a phenoxy resin containing a bisphenol acetophenone skeleton), "FX280" and "FX293" manufactured by Nippon Steel Chemical Materials Co., Ltd.; "YX7200B35", "YL7500BH30", "YX6954BH30", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290" and "YL7482" manufactured by Mitsubishi Chemical Corporation.
[0214] Examples of the polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, preferably polyvinyl butyral resin. Specific examples of the polyvinyl acetal resin include S-LEC BH series, BX series (e.g., BX-5Z), KS series (e.g., KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.
[0215] Examples of the polyolefin resin include ethylene copolymer resins such as low-density polyethylene, ultra-low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymers, ethylene-ethyl acrylate copolymers, and ethylene-methyl acrylate copolymers; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymers.
[0216] Examples of the polybutadiene resin include resins containing a hydrogenated polybutadiene skeleton, hydroxyl-containing polybutadiene resins, phenolic hydroxyl-containing polybutadiene resins, carboxyl-containing polybutadiene resins, acid anhydride-containing polybutadiene resins, epoxy-containing polybutadiene resins, isocyanate-containing polybutadiene resins, urethane-containing polybutadiene resins, and polyphenylene ether-polybutadiene resins.
[0217] Specific examples of polyamide-imide resins include "VYLOMAX HR11NN" and "VYLOMAX HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins include modified polyamide-imides such as "KS9100" and "KS9300" (polyamide-imide containing a polysiloxane skeleton) manufactured by Hitachi Chemical Co., Ltd.
[0218] Specific examples of the polyethersulfone resin include "PES5003P" manufactured by Sumitomo Chemical Co., Ltd. and the like.
[0219] Specific examples of the polysulfone resin include polysulfone "P1700" and "P3500" manufactured by Solvay Advanced Polymers.
[0220] Specific examples of the polyphenylene ether resin include "NORYL SA90" manufactured by SABIC, etc. Specific examples of the polyetherimide resin include "ULTEM" manufactured by GE, etc.
[0221] As polycarbonate resins, hydroxyl-containing carbonate resins, phenolic hydroxyl-containing carbonate resins, carboxyl-containing carbonate resins, anhydride-containing carbonate resins, isocyanate-containing carbonate resins, urethane-containing carbonate resins, etc. can be cited. As specific examples of carbonate resins, "FPC0220" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002", "T6001" (polycarbonate diol) manufactured by Asahi Kasei Corporation, "C-1090", "C-2090", "C-3090" (polycarbonate diol) manufactured by Kuraray Co., Ltd., etc. can be cited. As specific examples of polyetheretherketone resins, "SUMIPLOY K" manufactured by Sumitomo Chemical Co., Ltd., etc. can be cited.
[0222] Examples of the polyester resin include polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polybutylene naphthalate, polytrimethylene terephthalate, polytrimethylene naphthalate, and polycyclohexane dimethyl terephthalate.
[0223] From the viewpoint of significantly achieving the effects of the present invention, the weight average molecular weight (Mw) of the (F) thermoplastic resin is preferably at least 5,000, more preferably at least 8,000, further preferably at least 10,000, particularly preferably at least 20,000, preferably at most 100,000, more preferably at most 70,000, further preferably at most 60,000, particularly preferably at most 50,000.
[0224] When the total non-volatile components in the resin composition are set to 100% by mass, the content of the (F) thermoplastic resin in the resin composition is, for example, 0% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 0.5% by mass or more, further more preferably 1% by mass or more, particularly preferably 2% by mass or more, and the upper limit is preferably 50% by mass or less, more preferably 40% by mass or less, further more preferably 30% by mass or less, further more preferably 25% by mass or less, further more preferably 20% by mass or less, particularly preferably 15% by mass or less.
[0225] When (C) inorganic filler is included, the content of (F) thermoplastic resin when the non-volatile components other than (C) inorganic filler in the resin composition are set to 100% by mass is, for example, 0% by mass or more, preferably 0.01% by mass or more, better 0.1% by mass or more, further better 1% by mass or more, further better 5% by mass or more, particularly better 8% by mass or more, and the upper limit is preferably 90% by mass or less, better 70% by mass or less, further better 50% by mass or less, further better 40% by mass or less, particularly better 30% by mass or less.
[0226] The mass ratio of the (F) thermoplastic resin to the (A) maleimide resin in the resin composition (content of the (F) component / content of the (A) component) is, for example, 0 or more, preferably 0.001 or more, more preferably 0.01 or more, further preferably 0.1 or more, particularly preferably 0.3 or more, and the upper limit is preferably 20 or less, more preferably 10 or less, further preferably 5, further preferably 2 or less, particularly preferably 1.5 or less.
[0227] The total content of (A) maleimide resin, (B) acid salt of amine compound represented by formula (I), (C) inorganic filler, (D) anionic polymerizable curing agent, (E) epoxy resin and (F) thermoplastic resin in resin composition is not particularly limited, and when all non-volatile components in resin composition are set to 100% by mass, for example, more than 30% by mass, more than 50% by mass, more than 70% by mass, preferably more than 80% by mass, more preferably more than 85% by mass, further more preferably more than 90% by mass, further more preferably more than 95% by mass, further more preferably more than 98% by mass, particularly preferably more than 99% by mass. The upper limit of the total content of (A) maleimide resin, (B) acid salt of amine compound represented by formula (I), (C) inorganic filler, (D) anionic polymerizable curing agent, (E) epoxy resin and (F) thermoplastic resin in resin composition is not particularly limited, and can be set to, for example, less than 100% by mass.
[0228] <(G) Radical Polymerization Initiator>
[0229] The resin composition of the present invention may further contain (G) a radical polymerization initiator as an optional component. The (G) radical polymerization initiator is preferably a thermal polymerization initiator that generates radicals when heated. The (G) radical polymerization initiator may be used alone or in any combination of two or more.
[0230] (G) As a radical polymerization initiator, a peroxide radical polymerization initiator, an azo radical polymerization initiator etc. are mentioned, for example. Among them, a peroxide radical polymerization initiator is preferred.
[0231] Examples of the peroxide-based free radical polymerization initiator include hydroperoxide compounds such as 1,1,3,3-tetramethylbutyl hydroperoxide; dialkyl peroxide compounds such as tert-butyl isopropyl peroxide, di-tert-butyl peroxide, di-tert-hexyl peroxide, dicumyl peroxide, 1,4-bis(1-tert-butylperoxy-1-methylethyl)benzene, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane; dilauroyl peroxide, didecanoyl peroxide, dicyclohexyl peroxydicarbonate, bis(4-tert-butylcyclohexyl)peroxy Peroxy diacyl compounds such as dicarbonate; tert-butyl peroxyacetate, tert-butyl peroxybenzoate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyneodecanoate, tert-hexyl peroxyisopropyl monocarbonate, tert-butyl peroxylaurate, 1,1-dimethylpropyl 2-ethylperoxyhexanoate, tert-butyl 2-ethylperoxyhexanoate, tert-butyl 3,5,5-trimethylperoxyhexanoate, tert-butyl peroxy-2-ethylhexyl monocarbonate, tert-butyl peroxymaleate and other peroxy ester compounds, etc.
[0232] Examples of the azo radical polymerization initiator include azo nitrile compounds such as 2,2′-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2′-azobis(2,4-dimethylvaleronitrile), 2,2′-azobisisobutyronitrile, 2,2′-azobis(2-methylbutyronitrile), 1,1′-azobis(cyclohexane-1-carbonitrile), 1-[(1-cyano-1-methylethyl)azo]formamide, and 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile; 2,2′-azobis[2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide], 2,2′-azobis[2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide], Azo amide compounds such as 2,2′-azobis[2-methyl-N-[2-(1-hydroxybutyl)]-propionamide], 2,2′-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], 2,2′-azobis(2-methylpropionamide) dihydrate, 2,2′-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2′-azobis(N-butyl-2-methylpropionamide), and 2,2′-azobis(N-cyclohexyl-2-methylpropionamide); alkyl azo compounds such as 2,2′-azobis(2,4,4-trimethylpentane) and 2,2′-azobis(2-methylpropane); and the like.
[0233] (G) Commercially available products of the radical polymerization initiator include, for example, "PERBUTYL C", "PERBUTYL A", "PERBUTYL P", "PERBUTYL L", "PERBUTYL O", "PERBUTYL ND", "PERBUTYL Z", "PERBUTYL I", "PERCUMYL P", "PERCUMYL D", "PERHEXYL D", "PERHEXYL A", "PERHEXYL I", "PERHEXYL Z", "PERHEXYL ND", "PERHEXYL O", and "PERHEXYL PV" manufactured by NOF Corporation.
[0234] The content of the (G) radical polymerization initiator in the resin composition is not particularly limited. When the non-volatile component in the resin composition is set to 100% by mass, it is preferably 3% by mass or less, more preferably 2% by mass or less, further preferably 1% by mass or less, further preferably 0.7% by mass or less, and particularly preferably 0.5% by mass or less. The lower limit is not particularly limited. When the non-volatile component in the resin composition is set to 100% by mass, it is, for example, 0% by mass or more, 0.0001% by mass or more, preferably 0.0005% by mass or more, more preferably 0.001% by mass or more, further preferably 0.01% by mass or more, and particularly preferably 0.1% by mass or more.
[0235] <(H) Other additives>
[0236] The resin composition of the present invention may further contain any additives. Examples of such additives include curing accelerators other than the acid salt of the amine compound represented by formula (I), such as phosphorus curing accelerators, urea curing accelerators, guanidine curing accelerators, imidazole curing accelerators, and metal curing accelerators; free radical polymerizable compounds having allyl, vinylphenyl, acryloyl, methacryloyl, etc.; organic fillers such as rubber particles; organic metal compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone leveling agents and acrylic polymer leveling agents; thickeners such as Benton and montmorillonite; defoamers such as silicone defoamers, acrylic defoamers, fluorine defoamers, and vinyl resin defoamers; benzotriazole ultraviolet absorbers UV absorbers such as absorbents; adhesion enhancers such as urea silane; adhesion imparting agents such as triazole-type adhesion imparting agents, tetrazole-type adhesion imparting agents, and triazine-type adhesion imparting agents; antioxidants such as hindered phenol-type antioxidants; fluorescent whitening agents such as stilbene derivatives; surfactants such as fluorine-type surfactants and silicone-type surfactants; flame retardants such as phosphorus-type flame retardants (such as phosphate compounds, phosphazene compounds, phosphonic acid compounds, and red phosphorus), nitrogen-type flame retardants (such as melamine sulfate), halogen-type flame retardants, and inorganic flame retardants (such as antimony trioxide); dispersants such as phosphate-type dispersants, polyoxyalkylene dispersants, acetylene dispersants, silicone-type dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate stabilizers, titanate stabilizers, aluminate stabilizers, zirconate stabilizers, isocyanate stabilizers, carboxylic acid stabilizers, and carboxylic anhydride stabilizers, etc. (H) Other additives may be used alone or in combination of two or more at any ratio. A person skilled in the art can appropriately set the content of (H) other additives.
[0237] <(I) Organic Solvent>
[0238] The resin composition of the present invention sometimes further contains an arbitrary organic solvent. As (I) organic solvent, a known organic solvent can be used appropriately, and its type is not particularly limited. As (I) organic solvent, for example, ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, and anisole; alcohol solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, and diethylene glycol ethyl ether acetate (ethyl diglycol Ether ester solvents such as acetate, γ-butyrolactone, and methyl methoxypropionate; ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butyl carbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. (I) The organic solvent can be used alone or in combination of two or more in any proportion.
[0239] The content of (I) organic solvent in the varnish-like resin composition before drying is not particularly limited. When all the ingredients in the resin composition are set to 100% by mass, for example, 40% by mass or less, 30% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 8% by mass or less, and particularly preferably 6% by mass or less. When all the ingredients in the resin composition are set to 100% by mass, the lower limit of the content of (J) organic solvent in the varnish-like resin composition before drying can be 0% by mass, or greater than 0% by mass. The content of (I) organic solvent in the dried resin composition forming the resin composition layer in the resin sheet is not particularly limited. When all the ingredients in the resin composition are set to 100% by mass, it is preferably 5% by mass or less, more preferably 3% by mass or less, further preferably 2% by mass or less, and particularly preferably 1% by mass or less. When all the ingredients in the resin composition are set to 100% by mass, the lower limit of the content of (J) organic solvent in the dried resin composition forming the resin composition layer in the resin sheet can be 0% by mass, or greater than 0% by mass.
[0240] <Method for producing resin composition>
[0241] The resin composition of the present invention can be manufactured as follows: in any preparation container, in any order and / or partially or entirely, (A) maleimide resin, (B) acid salt of amine compound represented by formula (I), (C) inorganic filler material as required, (D) anionic polymerizable curing agent as required, (E) epoxy resin as required, (F) thermoplastic resin as required, (G) free radical polymerization initiator as required, (H) other additives as required, and (I) organic solvent as required and mixed. In addition, in the process of adding each component and mixing, the temperature can be appropriately set, and heating and / or cooling can be performed temporarily or all the time. In addition, in the process of adding and mixing or thereafter, the resin composition can be stirred or vibrated with a stirring device or oscillating device such as a mixer and uniformly dispersed. In addition, deaeration can be performed under low pressure conditions such as under vacuum while stirring or vibrating.
[0242] <Characteristics of Resin Composition>
[0243] The resin composition of the present invention comprises (A) a maleimide resin and (B) an acid salt of an amine compound represented by formula (I). According to such a resin composition, a cured product having a high glass transition temperature and maintaining excellent copper foil adhesion strength even after a HAST test can be obtained.
[0244] The cured product of the resin composition of the present invention has a high glass transition temperature (Tg). Therefore, for example, the glass transition temperature (Tg) when measured as in the following Test Example 1 is preferably 100°C or more, more preferably 120°C or more, further preferably 130°C or more, further more preferably 140°C or more, further more preferably 145°C or more, and particularly preferably 150°C or more.
[0245] The cured product of the resin composition of the present invention has the feature that the copper foil adhesion strength (copper foil peeling strength) after accelerated environmental test (HAST) is high. Therefore, the copper foil adhesion strength (copper foil peeling strength) after the accelerated environmental test (HAST) measured according to JIS C6481 as described in the following test example 2 is preferably more than 0.1kgf / cm, more preferably more than 0.2kgf / cm, further more preferably more than 0.3kgf / cm, further more preferably more than 0.35kgf / cm, particularly preferably more than 0.4kgf / cm. In addition, the copper foil adhesion strength (copper foil peeling strength) before the accelerated environmental test (HAST) measured in the same manner is preferably more than 0.1kgf / cm, more preferably more than 0.2kgf / cm, further more preferably more than 0.4kgf / cm, further more preferably more than 0.5kgf / cm, further more preferably more than 0.6kgf / cm, particularly preferably more than 0.65kgf / cm. In addition, the strength reduction rate of the copper foil adhesion strength after the accelerated environmental test (HAST) relative to the copper foil adhesion strength before the accelerated environmental test (HAST) [(1-copper foil adhesion strength after HAST / copper foil adhesion strength before HAST) × 100 (%)] is preferably 80% or less, more preferably 70% or less, further preferably 60% or less, further preferably 55% or less, and particularly preferably 50% or less. The lower limit of the strength reduction rate of the copper foil adhesion strength after the accelerated environmental test (HAST) relative to the copper foil adhesion strength before the accelerated environmental test (HAST) is not limited, and can be, for example, 1% or more.
[0246] <Application of resin composition>
[0247] The resin composition of the present invention can be preferably used as a resin composition for insulating purposes, in particular, a resin composition for forming an insulating layer. Specifically, the resin composition of the present invention can be preferably used as a resin composition for forming the insulating layer (resin composition for forming an insulating layer for forming a conductor layer) for forming a conductor layer (including a rewiring layer) formed on the insulating layer. In addition, in the printed wiring board described later, the resin composition of the present invention can be preferably used as a resin composition for forming the insulating layer of the printed wiring board (resin composition for forming the insulating layer of the printed wiring board). The resin composition of the present invention can also be widely used in the applications requiring resin compositions such as resin sheets, prepregs, etc., solder resists, bottom filling materials, chip bonding materials, semiconductor sealing materials, hole-filling resins, and component embedding resins.
[0248] In addition, for example, when a semiconductor chip package is manufactured through the following steps (1) to (6), the resin composition of the present invention can also be preferably used as a resin composition for a rewiring forming layer (resin composition for forming a rewiring forming layer) as an insulating layer for forming a rewiring layer and a resin composition for sealing a semiconductor chip (resin composition for sealing a semiconductor chip). When manufacturing a semiconductor chip package, a rewiring layer can be further formed on the sealing layer.
[0249] (1) A step of laminating a temporary fixing film on a substrate;
[0250] (2) A step of temporarily fixing the semiconductor chip on a temporary fixing film;
[0251] (3) a step of forming a sealing layer on a semiconductor chip;
[0252] (4) a step of peeling the substrate and the temporary fixing film from the semiconductor chip;
[0253] (5) forming a rewiring forming layer as an insulating layer on the surface of the semiconductor chip from which the substrate and the temporary fixing film have been peeled off; and
[0254] (6) A step of forming a rewiring layer as a conductor layer on the rewiring formation layer.
[0255] Furthermore, the resin composition of the present invention can provide an insulating layer having good component embedding properties, and therefore can be preferably used even when the printed wiring board is a component-embedded wiring board.
[0256] <Sheet-like laminated material>
[0257] The resin composition of the present invention can also be used by coating in a varnish state, but is generally preferably used in the form of a sheet-like laminate containing the resin composition in industrial terms.
[0258] As the sheet-like lamination material, the following resin sheets and prepregs are preferred.
[0259] In one embodiment, the resin sheet includes a support and a resin composition layer provided on the support, and the resin composition layer is formed from the resin composition of the present invention.
[0260] From the viewpoint of thinning of printed wiring board and providing a cured product with excellent insulation even if the cured product of the resin composition is a film, the thickness of the resin composition layer is preferably below 50 μm, more preferably below 40 μm. The lower limit of the thickness of the resin composition layer is not particularly limited, and can usually be set to above 5 μm, above 10 μm, etc.
[0261] Examples of the support include films formed of a plastic material, metal foil and release paper, and films formed of a plastic material and metal foil are preferred.
[0262] When a film formed of a plastic material is used as a support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes referred to as "PET") and polyethylene naphthalate (hereinafter sometimes referred to as "PEN"), polycarbonate (hereinafter sometimes referred to as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among them, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0263] When a metal foil is used as a support, examples of the metal foil include copper foil and aluminum foil, preferably copper foil. As the copper foil, a foil formed of a single metal of copper can be used, or a foil formed of an alloy of copper and other metals (such as tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) can be used.
[0264] The surface of the support that contacts the resin composition layer may be subjected to matte treatment, corona treatment, or antistatic treatment.
[0265] In addition, as a support, a support with a release layer having a release layer on the surface bonded to the resin composition layer can be used. As a release agent for the release layer of the support with a release layer, for example, one or more release agents selected from alkyd resins, polyolefin resins, polyurethane resins and silicone resins can be cited. The support with a release layer can use a commercial product, for example, a PET film having a release layer with an alkyd resin release agent as a main component, "SK-1", "AL-5", "AL-7" manufactured by Lintec, "Lumirror T60" manufactured by Toray Industries, "Purex" manufactured by Teijin, "Unipeel" manufactured by UNITIKA, etc.
[0266] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the thickness of the entire support with a release layer is preferably in the above range.
[0267] In one embodiment, the resin sheet may further include an arbitrary layer as required. As the arbitrary layer, for example, a protective film selected according to the support body and arranged on the surface of the resin composition layer that is not bonded to the support body (i.e., the surface on the opposite side of the support body) can be cited. The thickness of the protective film is not particularly limited, for example, 1 μm to 40 μm. By laminating the protective film, dust and the like can be prevented from adhering to the surface of the resin composition layer or from being damaged on the surface of the resin composition layer.
[0268] The resin sheet can be manufactured, for example, by directly preparing a liquid (varnish-like) resin composition, or by dissolving the resin composition in an organic solvent to prepare a liquid (varnish-like) resin composition, applying the liquid (varnish-like) resin composition on a support using a die coater or the like, and then drying to form a resin composition layer.
[0269] Examples of the organic solvent include the same organic solvents as those described as components of the resin composition. The organic solvent may be used alone or in combination of two or more.
[0270] Drying can be implemented by known methods such as heating and hot air blowing. The drying conditions are not particularly limited, and the drying is performed in a manner such that the content of the organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. Depending on the boiling point of the organic solvent in the resin composition, for example, in the case of a resin composition containing 30% by mass to 60% by mass of an organic solvent, the resin composition layer can be formed by drying at 50° C. to 150° C. for 3 minutes to 10 minutes.
[0271] The resin sheet can be stored in a roll. When the resin sheet has a protective film, the resin sheet can be used by peeling off the protective film.
[0272] In one embodiment, the prepreg is formed by impregnating a sheet-like fiber base material with the resin composition of the present invention.
[0273] The sheet-like fiber substrate used for the prepreg is not particularly limited, and glass cloth, aramid nonwoven fabric, liquid crystal polymer nonwoven fabric, etc. can be used as materials commonly used as prepreg substrates. From the viewpoint of thinning the printed wiring board, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, further preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited, and is usually 10 μm or more.
[0274] The prepreg can be produced by a known method such as a hot melt method or a solvent method.
[0275] The thickness of the prepreg can be set to the same range as that of the resin composition layer in the above-mentioned resin sheet.
[0276] The sheet-like laminated material of the present invention can be preferably used to form an insulating layer of a printed wiring board (for an insulating layer of a printed wiring board), and can be more preferably used to form an interlayer insulating layer of a printed wiring board (for an interlayer insulating layer of a printed wiring board).
[0277] <Printed wiring board>
[0278] The printed wiring board of the present invention includes an insulating layer formed of a cured product obtained by curing the resin composition of the present invention.
[0279] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet and by a method including the following steps (I) and (II):
[0280] (I) a step of laminating a resin sheet on the inner substrate in such a manner that the resin composition layer of the resin sheet is bonded to the inner substrate;
[0281] (II) A step of curing (for example, thermally curing) the resin composition layer to form an insulating layer.
[0282] The "inner substrate" used in step (I) refers to a member that becomes a substrate of a printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, a thermosetting polyphenylene ether substrate, and the like. In addition, the substrate may have a conductor layer on one or both sides thereof, and the conductor layer may be patterned. An inner substrate having a conductor layer (circuit) formed on one or both sides of a substrate is sometimes referred to as an "inner circuit substrate". In addition, an intermediate product in which an insulating layer and / or a conductor layer should be further formed when manufacturing a printed wiring board is also included in the "inner substrate" referred to in the present invention. In the case where the printed wiring board is a circuit board with built-in components, an inner substrate with built-in components may also be used.
[0283] The lamination of inner substrate and resin sheet can be carried out by, for example, heating and pressing the resin sheet to the inner substrate from the support body side. As a member (hereinafter also referred to as "heating and pressing member") for heating and pressing the resin sheet to the inner substrate, for example, a heated metal plate (SUS mirror plate) or a metal roller (SUS roller) etc. can be cited. It should be noted that it is better not to press the heating and pressing member directly on the resin sheet, but to press it via an elastic material such as heat-resistant rubber so that the resin sheet fully conforms to the surface unevenness of the inner substrate.
[0284] The lamination of the inner substrate and the resin sheet can be implemented by vacuum lamination. In the vacuum lamination, the heating and pressing temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the heating and pressing pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the heating and pressing time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. Lamination can be preferably implemented under reduced pressure conditions of 26.7hPa or less.
[0285] Lamination can be performed by a commercially available vacuum laminator, for example, a vacuum pressure laminator manufactured by Meiki Mfg. Co., Ltd., a vacuum applicator manufactured by Nikko-Materials Co., Ltd., and a batch vacuum pressure laminator.
[0286] After lamination, the laminated resin sheet can be smoothed by, for example, applying pressure to the heating and pressing member from the support body side under normal pressure (atmospheric pressure). The pressing conditions for the smoothing treatment can be the same as the heating and pressing conditions for the above-mentioned lamination. The smoothing treatment can be performed by a commercially available vacuum laminator. It should be noted that the lamination and smoothing treatment can be performed continuously using the above-mentioned commercially available vacuum laminator.
[0287] The support may be removed between step (I) and step (II), or may be removed after step (II).
[0288] In step (II), the resin composition layer is cured (eg, thermally cured) to form an insulating layer composed of a cured product of the resin composition. The curing conditions of the resin composition layer are not particularly limited, and conditions generally used when forming an insulating layer of a printed wiring board can be used.
[0289] For example, the thermal curing conditions of the resin composition layer vary depending on the type of the resin composition, and in one embodiment, the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and further preferably 170° C. to 210° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and further preferably 15 minutes to 100 minutes.
[0290] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature of 50°C to 120°C, preferably 60°C to 115°C, more preferably 70°C to 110°C, for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and further preferably 15 minutes to 100 minutes.
[0291] When manufacturing a printed wiring board, it is also possible to further implement a process (III) of opening holes in the insulating layer, a process (IV) of roughening the insulating layer, and a process (V) of forming a conductor layer. These processes (III) to (V) can be implemented according to various methods known to those skilled in the art used in the manufacture of printed wiring boards. It should be noted that when the support body is removed after process (II), the removal of the support body can be implemented between process (II) and process (III), between process (III) and process (IV), or between process (IV) and process (V). In addition, the formation of the insulating layer and the conductor layer of processes (II) to (V) can be repeatedly implemented as needed to form a multilayer wiring board.
[0292] In another embodiment, the printed wiring board of the present invention can be produced using the above-mentioned prepreg. The production method is basically the same as that in the case of using a resin sheet.
[0293] Step (III) is a step of drilling holes in the insulating layer, thereby forming holes such as through holes and vias in the insulating layer. Step (III) can be carried out using, for example, a drill, laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The size and shape of the hole can be appropriately determined according to the design of the printed wiring board.
[0294] Step (IV) is a step of roughening the insulating layer. Usually, in step (IV), smear removal is also performed. The steps and conditions of the roughening treatment are not particularly limited, and the known steps and conditions commonly used when forming the insulating layer of the printed wiring board can be used. For example, the insulating layer can be roughened by swelling treatment using a swelling solution, roughening treatment using an oxidant, and neutralization treatment using a neutralizing solution.
[0295] The swelling liquid used in the roughening treatment is not particularly limited, and alkali solutions, surfactant solutions, etc. can be listed. Alkaline solutions are preferred, and sodium hydroxide solutions and potassium hydroxide solutions are more preferred as the alkaline solutions. Commercially available swelling liquids include, for example, "Swelling Dip Securiganth P" and "Swelling Dip Securiganth SBU" manufactured by Atotech Japan Co., Ltd. The swelling treatment using the swelling liquid is not particularly limited, and can be carried out, for example, by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 minute to 20 minutes. From the viewpoint of controlling the swelling of the resin of the insulating layer to an appropriate level, it is better to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 minutes to 15 minutes.
[0296] As the oxidant used in the roughening treatment, there is no particular limitation, and examples thereof include alkaline permanganate solutions obtained by dissolving potassium permanganate or sodium permanganate in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidant such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidant solution heated to 60° C. to 100° C. for 10 to 30 minutes. In addition, the concentration of permanganate in the alkaline permanganate solution is preferably 5% to 10% by mass. As commercially available oxidants, examples thereof include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing solution Securighanth P" manufactured by Atotech Japan.
[0297] The neutralizing solution used for the roughening treatment is preferably an acidic aqueous solution, and examples of commercially available products include "Reduction solution Securiganth P" manufactured by Atotech Japan Ltd.
[0298] The treatment with a neutralizing solution can be performed by immersing the treated surface subjected to the roughening treatment with an oxidizing agent in a neutralizing solution at 30° C. to 80° C. for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the target object subjected to the roughening treatment with an oxidizing agent is immersed in a neutralizing solution at 40° C. to 70° C. for 5 to 20 minutes is preferred.
[0299] In one embodiment, the arithmetic mean roughness (Ra) of the insulating layer surface after roughening treatment is not particularly limited, preferably less than 500nm, more preferably less than 400nm, and further preferably less than 300nm. There is no particular limitation on the lower limit, for example, it can be set to more than 1nm, more than 2nm, etc. In addition, the root mean square roughness (Rq) of the insulating layer surface after roughening treatment is preferably less than 500nm, more preferably less than 400nm, and further preferably less than 300nm. There is no particular limitation on the lower limit, for example, it can be set to more than 1nm, more than 2nm, etc. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.
[0300] Step (V) is a step of forming a conductor layer, and a conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer comprises one or more metals selected from the group formed by gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer can be a single metal layer or an alloy layer. As the alloy layer, for example, a layer formed by an alloy of two or more metals selected from the above group (for example, a nickel-chromium alloy, a copper-nickel alloy and a copper-titanium alloy) can be listed. Among them, from the perspective of versatility, cost, and ease of patterning of the conductor layer, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy, copper-nickel alloy, or copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy is more preferred, and a single metal layer of copper is further preferred.
[0301] The conductor layer may be a single layer structure or a multilayer structure in which two or more single metal layers or alloy layers formed of different types of metals or alloys are stacked. When the conductor layer is a multilayer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium or an alloy layer of a nickel-chromium alloy.
[0302] The thickness of the conductor layer varies depending on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, preferably 5 μm to 30 μm.
[0303] In one embodiment, the conductor layer can be formed by plating. For example, the conductor layer having a desired wiring pattern can be formed by plating on the surface of the insulating layer by a conventionally known technique such as a semi-additive method or a full-additive method. From the perspective of manufacturing simplicity, it is preferably formed by a semi-additive method. An example of forming a conductor layer by a semi-additive method is shown below.
[0304] First, a plating seed layer is formed on the surface of the insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a portion of the plating seed layer corresponding to the desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Then, the unnecessary plating seed layer is removed by etching or the like, thereby forming a conductor layer having a desired wiring pattern.
[0305] In other embodiments, the conductor layer can be formed using a metal foil. When a metal foil is used to form a conductor layer, step (V) is preferably implemented between step (I) and step (II). For example, after step (I), the support is removed and a metal foil is laminated on the surface of the exposed resin composition layer. The lamination of the resin composition layer and the metal foil can be implemented by a vacuum lamination method. The lamination conditions can be set to be the same as those described for step (I). Next, step (II) is implemented to form an insulating layer. Then, the metal foil on the insulating layer can be used to form a conductor layer with a desired wiring pattern by conventionally known techniques such as a subtractive method and an improved semi-additive method.
[0306] The metal foil can be produced by a known method such as electrolysis or rolling. Examples of commercially available metal foils include HLP foil and JXUT-III foil manufactured by JX Metals, and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Smelting Co., Ltd.
[0307] <Semiconductor Device>
[0308] The semiconductor device of the present invention includes the printed wiring board of the present invention. The semiconductor device of the present invention can be produced using the printed wiring board of the present invention.
[0309] Examples of the semiconductor device include various semiconductor devices used in electronic products (eg, computers, mobile phones, digital cameras, and televisions) and vehicles (eg, motorcycles, cars, trains, ships, and aircraft).
[0310] Example
[0311] Hereinafter, the present invention will be specifically described by way of examples. The present invention is not limited to these examples. It should be noted that, hereinafter, unless otherwise expressly stated, "parts" and "%" indicating amounts refer to "parts by mass" and "% by mass", respectively. The temperature condition when the temperature is not particularly specified is at room temperature (23° C.), and the pressure condition when the pressure is not particularly specified is at atmospheric pressure (1 atm).
[0312] <Synthesis Example 1: Synthesis of Maleimide X>
[0313] Maleimide A (m=1.47, Mw / Mn=1.81) represented by the following formula was synthesized by the same method as in Synthesis Example 1 of KOKU Publication No. 2020-500211 to obtain a MEK solution of maleimide resin (non-volatile content 62% by mass).
[0314] [Chemistry 11]
[0315]
[0316] <Preparation Example 1: Preparation of DMAP-p-toluenesulfonate>
[0317] 2.0 g of 4-dimethylaminopyridine and 0.0164 mol of p-toluenesulfonic acid were weighed in a glass container, dimethyl sulfoxide was added so that the total solid content was 20% by weight, and the mixture was stirred for 30 minutes to dissolve, thereby preparing a DMAP-p-toluenesulfonate solution.
[0318] <Preparation Example 2: Preparation of DMAP-phthalate>
[0319] 2.0 g of 4-dimethylaminopyridine and 0.0164 mol of phthalic acid were weighed in a glass container, dimethyl sulfoxide was added so that the total solid content was 20% by weight, and the mixture was stirred for 30 minutes to dissolve, thereby preparing a DMAP-phthalate solution.
[0320] <Preparation Example 3: Preparation of DMAP-trimellitate>
[0321] 2.0 g of 4-dimethylaminopyridine and 0.0164 mol of trimellitic acid were weighed in a glass container, dimethyl sulfoxide was added so that the total solid content was 20% by weight, and the mixture was stirred for 30 minutes to dissolve, thereby preparing a DMAP-trimellitic acid solution.
[0322] <Examples 1 to 6, Comparative Examples 1 and 2: Preparation of Resin Compositions
[0323] Each component was weighed according to the mass ratio described in Table 1, and 5 parts of MEK and 15 parts of cyclohexanone were mixed and uniformly dispersed with a high-speed rotary mixer to prepare a varnish-like resin composition. The details of each component described in Table 1 are as follows.
[0324] (A) Maleimide resin
[0325] MIR-3000-70MT: maleimide resin with biphenyl skeleton, maleimide group equivalent weight 393 g / eq., toluene solution with non-volatile content of 70% by mass, manufactured by Nippon Kayaku Co., Ltd.
[0326] Maleimide X: a maleimide resin having an indane skeleton, maleimide group equivalent weight 428 g / eq., synthesized in Synthesis Example 1
[0327] SLK-6895-T90: maleimide resin having a carbon skeleton derived from dimer acid, maleimide group equivalent weight 345 g / eq., toluene solution containing 90% by mass of nonvolatile components, manufactured by Shin-Etsu Chemical Co., Ltd.
[0328] (B) Acid salt of an amine compound represented by formula (I)
[0329] DMAP-p-toluenesulfonate: non-volatile content 20% by mass, prepared in Preparation Example 1
[0330] DMAP-phthalate: non-volatile content 20% by mass, prepared in Preparation Example 2
[0331] DMAP-trimellitate: non-volatile content 20% by mass, prepared in Preparation Example 3
[0332] DMAP: 4-dimethylaminopyridine
[0333] 1B2PZ: 1-benzyl-2-phenylimidazole, manufactured by Shikoku Chemical Industry Co., Ltd.
[0334] (C) Inorganic filling materials
[0335] SO-C2: Spherical silica surface-treated with an amine alkoxysilane compound (Shin-Etsu Chemical Co., Ltd. "KBM573"), average particle size 0.5 μm, specific surface area 5.8 m 2 / g, made by Yaduma
[0336] (D) Anionic polymerizable curing agent
[0337] LA-3018-50P: phenolic curing agent, functional group equivalent 151 g / eq., 1-methoxy-2-propanol solution with a non-volatile content of 50% by mass, manufactured by DIC Corporation
[0338] SA90: phenolic curing agent, functional group equivalent 800g / eq., manufactured by SABIC
[0339] HPC-8000-65T: Active ester curing agent, functional group equivalent 223g / eq., toluene solution with non-volatile content 65%, manufactured by DIC Corporation
[0340] V-03: Carbodiimide curing agent, functional group equivalent 216 g / eq., toluene solution with non-volatile content of 50% by mass, manufactured by Nisshinbo Chemical Co., Ltd.
[0341] (E) Epoxy resin
[0342] HP-4032-SS: Naphthalene-based epoxy resin, functional group equivalent 144 g / eq., manufactured by DIC Corporation
[0343] NC3000L: biphenyl type epoxy resin, functional group equivalent 269g / eq., manufactured by Nippon Kayaku Co., Ltd.
[0344] (F) Thermoplastic resin
[0345] ·YX7553BH30: phenoxy resin, 1:1 solution of MEK and cyclohexanone with a non-volatile content of 30% by mass, manufactured by Mitsubishi Chemical Corporation
[0346] PIAD200: polyimide resin, a mixed solution of cyclohexanone, ethylene glycol dimethyl ether (Dimetril Glycol) and methylcyclohexane with a non-volatile content of 30%, manufactured by Arakawa Chemical Co., Ltd.
[0347] ·P2000: Styrene elastomer, manufactured by Asahi Kasei Corporation
[0348] (G) Radical polymerization initiator
[0349] PERHEXYLD: Peroxide-based free radical polymerization initiator, di-tert-hexyl peroxide, manufactured by NOF Corporation
[0350] <Test Example 1: Measurement of Glass Transition Temperature (Tg)>
[0351] (1) Preparation of Resin Sheet A Having a Resin Composition Layer Thickness of 40 μm
[0352] As a support, a polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm) having a release layer was prepared. The resin varnish obtained in the examples and comparative examples was evenly applied to the release layer of the support so that the thickness of the resin composition layer after drying reached 40 μm. Then, the resin composition was dried at 80 to 100° C. (90° C. on average) for 2 minutes to obtain a resin sheet A comprising a support and a resin composition layer.
[0353] (2) Preparation of solidified material
[0354] The obtained resin sheet A was cured in an oven at 190° C. for 90 minutes. The support was peeled off from the resin sheet A taken out of the oven to obtain a cured product of the resin composition layer.
[0355] (3) Determination of glass transition temperature (Tg)
[0356] The obtained cured product was cut into test pieces of about 5 mm in width and about 15 mm in length, and a thermomechanical analysis was performed by a tensile load method using a thermomechanical analyzer ("Thermo Plus TMA8310" manufactured by Rigaku Corporation). After the test piece was loaded into the device, the thermal expansion coefficient (ppm) was continuously measured twice under the measurement conditions of a load of 1 g and a heating rate of 5°C / min. According to the value of the linear expansion coefficient from 25°C to 150°C in the second measurement, the average linear expansion coefficient (ppm / °C) was calculated. In the second measurement, the glass transition temperature (Tg; °C) was calculated.
[0357] <Test Example 2: Measurement of Copper Foil Adhesion Strength (Copper Foil Peel Strength)>
[0358] Evaluation of metal foil adhesion was performed by measuring the copper foil peel strength according to the following procedure.
[0359] (1) Base treatment of copper foil
[0360] The shiny surface of the electrolytic copper foil ("3EC-III" manufactured by Mitsui Mining & Smelting Co., Ltd., thickness 35 μm) was etched 1 μm with a microetchant ("CZ8101" manufactured by Magco) to roughen the copper surface, and then a rust-proofing treatment (CL8300) was performed. Hereinafter, the copper foil whose surface was etched with the microetchant is sometimes referred to as "CZ copper foil". Furthermore, the copper foil was heated in an oven at 130° C. for 30 minutes to obtain a copper foil I having a roughened surface.
[0361] (2) Preparation of inner substrate
[0362] A glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.4 mm, "R1515A" manufactured by Panasonic Corporation) having copper foil on the surface and formed with an inner layer circuit was prepared. Both sides of the glass cloth-based epoxy resin double-sided copper-clad laminate were etched by 1 μm with a microetchant ("CZ8101" manufactured by Mager Corporation) to roughen the copper foil surface. Thus, an inner layer substrate having a CZ copper foil with a treated surface on the surface was obtained.
[0363] (3) Lamination of resin composition layers
[0364] The resin sheet A prepared in Test Example 1 (1) is laminated to both surfaces of the inner substrate. The lamination is performed using a batch vacuum pressure laminator (manufactured by Nikko-Materials, a two-stage build-up laminator, "CVP700") in such a way that the resin composition layer is in contact with the inner substrate. In addition, the lamination is performed as follows: after reducing the pressure for 30 seconds and adjusting the air pressure to below 13 hPa, the pressure is pressed at 120°C and a pressure of 0.74 MPa for 30 seconds. Next, the laminated resin sheet is hot-pressed at 100°C and a pressure of 0.5 MPa for 60 seconds. Then, the support is peeled off to expose the resin composition layer.
[0365] (4) Lamination of copper foil and curing of resin composition layer
[0366] The treated surface of copper foil I was laminated on the exposed resin composition layer under the same conditions as in the above-mentioned "(3) Lamination of resin composition layer". Furthermore, the resin composition layer was cured under the curing conditions of 200°C and 90 minutes to form an insulating layer comprising a cured product of the resin composition. Through the above operation, an evaluation substrate C having CZ copper foil laminated on both sides of the insulating layer was obtained. The evaluation substrate C had a layer structure of copper foil I / insulating layer / inner substrate / insulating layer / copper foil I.
[0367] (5) Measurement of copper foil adhesion strength (copper foil peel strength)
[0368] The evaluation substrate C was cut into small pieces of 150 mm × 30 mm. A cutter was used to introduce an incision in the copper foil I of the small piece, which surrounded a portion of 10 mm wide and 100 mm long. One end of the portion was peeled off and clamped with the clamp of a tensile testing machine (manufactured by TSE, AUTOCOM universal testing machine "AC-50C-SL"). At room temperature (25°C), it was stretched in the vertical direction at a speed of 50 mm / min, and the load [kgf / cm] when 35 mm was torn off was measured as the copper foil adhesion strength. For the measured samples, a 100-hour accelerated environmental test (HAST test) was carried out under the conditions of 130°C and 85% RH using a highly accelerated life tester (manufactured by Kusumoto Chemicals, "PM422"). Then, the copper foil adhesion strength after HAST was obtained by measuring the initial copper foil adhesion strength in the same manner as the measurement. The measurement was carried out in accordance with Japanese Industrial Standard JIS C6481.
[0369] The measurement results of the test examples are summarized in Table 1 below.
[0370] [Table 1]
[0371]
[0372] From the results shown in Table 1 above, it can be seen that by using a resin composition containing (A) a maleimide resin and (B) an acid salt of an amine compound represented by formula (I), a cured product can be obtained that maintains excellent copper foil adhesion strength even after an accelerated environmental test (HAST) and has a high glass transition temperature.
Claims
1. A resin composition, wherein Containing (A) a maleimide resin and (B) an acid salt of an amine compound represented by formula (I), In the formula, R 1 , R 2 , R 3 , R 4 and R 5 Each independently represents a hydrogen atom or a substituent.
2. The resin composition according to claim 1, wherein The amine compound represented by formula (I) is 4-dimethylaminopyridine.
3. The resin composition according to claim 1, wherein The component (B) includes a salt of an amine compound represented by the formula (I) and an organic acid selected from carboxylic acids and sulfonic acids.
4. The resin composition according to claim 1, wherein The component (B) comprises a salt of an amine compound represented by the formula (I) and an organic acid represented by any one of the formulas (IIa) to (IIc), In the formula, X represents -CO- or -SO2-; R a , R b , R c , R d , R e , R f and R g Each independently represents a hydrogen atom or a substituent.
5. The resin composition according to claim 1, wherein The component (B) contains an amine compound represented by the formula (I) and an acid dissociation constant (pK a ) is a salt of an organic acid with a value of 3.0 or less, In the case of polybasic organic acids, the acid dissociation constant (pK a ) is the lowest acid dissociation constant (pK) in the first stage a1 ).
6. The resin composition according to claim 1, wherein The component (B) includes a salt of an amine compound represented by the formula (I) and an organic acid selected from phthalic acid, trimellitic acid and p-toluenesulfonic acid.
7. The resin composition according to claim 1, wherein The mass ratio of the component (B) to the component (A), that is, the content of the component (B) / the content of the component (A) is 0.001 to 0.
1.
8. The resin composition according to claim 1, wherein The composition further comprises (C) an inorganic filler.
9. The resin composition according to claim 8, wherein The component (C) contains silicon dioxide.
10. The resin composition according to claim 8, wherein When the nonvolatile matter in the resin composition is 100% by mass, the content of the component (C) is 40% by mass or more.
11. The resin composition according to claim 1, wherein When the nonvolatile component in the resin composition is 100 mass %, the content of the anionic polymerizable curing agent (D) is 0 mass % to 20 mass %.
12. The resin composition according to claim 1, wherein When the nonvolatile component in the resin composition is 100 mass %, the content of the epoxy resin (E) is 0 mass % to 20 mass %.
13. The resin composition according to claim 1, wherein When the nonvolatile component in the resin composition is 100% by mass, the content of the (F) thermoplastic resin is 0% by mass to 30% by mass.
14. The resin composition according to claim 1, wherein The glass transition temperature (Tg) of the cured product of the resin composition is 140° C. or higher.
15. The resin composition according to claim 1, which is used for forming an insulating layer of a printed wiring board.
16. A cured product of the resin composition according to any one of claims 1 to 15.
17. A resin sheet, wherein: A resin composition layer comprising a support and the resin composition according to any one of claims 1 to 15 and provided on the support.
18. A printed wiring board, wherein: An insulating layer is provided which is formed of a cured product of the resin composition according to any one of claims 1 to 15.
19. A semiconductor device, wherein: A printed wiring board comprising the method according to claim 18.
20. A maleimide resin curing accelerator, wherein: An acid salt containing an amine compound represented by formula (I), In the formula, R 1 , R 2 , R 3 , R 4 and R 5 Each independently represents a hydrogen atom or a substituent.